Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

Acorn review: Biochar and its applications in US forestry - Gaurav Dhungel; Justin Baker; Jesse D. Henderson; Rachel Cook (Forest Ecology and Management, 2026)

Saffron harvestability detection with deep neural networks for just-in-time harvesting - Carter T. Noh; Nathan Jones; Douglas D. Cook (Biosystems Engineering, 2026)

Clinical and pathological assessment of the calystegines in Ipomoea carnea in a goat model - Daniel Cook; Bryan L. Stegelmeier; Dale R. Gardner; Franklin Riet-Correa; Clinton A. Stonecipher; Kevin D. Welch (Toxicon, 2026)

Isotope metrics refine herbivory among three nominally herbivorous reef fishes of socio-ecological importance - Joshua Pi; Stephane Martinez; Dana T. Cook; Milo Tasopulu; John Rulmal; Michelle J. Paddack; Nicole L. Crane; Giacomo Bernardi; Jonathan D. Cybulski; Kelton W. McMahon (Coral Reefs, 2026)
Herbivorous coral reef fishes are often assigned to different functional groups based on feeding mode and presumed ecosystem processes, such as algal removal ( i.e. , functional herbivory). However, these functional assignments do not necessarily identify assimilated resources nor predict nutritional pathways supporting fish biomass. We used stable carbon and nitrogen isotopes of amino acids to refine our understanding of herbivory among three nominally herbivorous fishes: Chlorurus spilurus , Ctenochaetus striatus , and Naso lituratus . Amino acid carbon isotope fingerprinting indicated much higher and more variable algal carbon contribution for N. lituratus (52.0% [22.0–84.1]) than C. spilurus (5.4% [0.9–17.8]) or C. striatus (4.8% [0.8–15.6]), which were corroborated by low trophic transfer values of N. lituratus ( Δδ 15 N Glu-Lys = 6.0 ± 0.9‰), high source δ 15 N Lys values (4.7 ± 1.0‰), and low microbial reworking ΣV values (0.9 ± 0.2). Conversely, higher Δδ 15 N Glu-Lys values of C. spilurus (7.9 ± 0.9‰) and C. striatus (9.0 ± 1.1‰) coupled with low δ 15 N Lys values (3.6 ± 1.0‰; 3.6 ± 1.1‰, respectively) and higher ΣV values (1.4 ± 0.2; 1.3 ± 0.2, respectively) indicated increased reliance on heterotrophically recycled production ( e.g. , bacteria, detritus, sponge tissue, mucus). Taken together, these data indicate N. lituratus as the most algivorous among our study species, while its broad source credible intervals may reflect epibiont assimilation, algal source variability, or intraspecific dietary variation. By linking carbon source assimilation and trophic transfer at the molecular level, we show that functionally “herbivorous” fishes can occupy distinct nutritional niches and that nutritional and functional definitions of herbivory may not always align.

Urinary biomarkers of PAHs, VOCs, OPEs, and metal(loid)s in firefighters responding in the wildland urban interface (WUI) - Miriam M. Calkins; Alexander C. Mayer; Derek J. Urwin; Steve Bertke; Christine Toennis; Shawn C. Beitel; Jeff Hughes; Jamie Gabriel; Antonia M. Calafat; Christopher M. Reese; Julianne Cook Botelho; Maria Ospina; et al. (International Journal of Hygiene and Environmental Health, 2026)

Longitudinal surface-based morphometry reveals potential MRI biomarkers correlated with multidimensional brain health measures - Robyn A. Honea; Ankit Patel; William Guiler; Mark D’Esposito; Sandra Bond Chapman; Lori G. Cook; Jeffrey S. Spence (Brain Imaging and Behavior, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Genes Versus Environment: Body Size Variation Among Recruitment Cohorts of Dungeness Crab - James L. Dimond; Sarah K. Grossman; Emily V. Buckner; Claire E. Cook; Katelyn M. Bosley; Elizabeth D. Tobin; Julie S. Barber (Molecular Ecology, 2026)
Understanding the drivers of phenotypic variation is key to disentangling the evolutionary and environmental forces that shape patterns of trait variation within and among populations. In Dungeness crab, settlement‐stage megalopae exhibit striking seasonal variation in body size, with early season cohorts consistently larger than later ones. This pattern may result from genetically distinct larval sources or environmentally induced plasticity following the temperature–size rule, which predicts larger body size at cooler temperatures. Here, we evaluated the relative contributions of these potential drivers by analysing megalopae size, regional sea surface temperatures and whole‐genome resequencing data from megalopae collected across the ~5‐month settlement season throughout Washington, USA. Genomic analyses revealed a subtle coastal ancestry signal in early‐arriving megalopae, supporting the hypothesis that these megalopae are of coastal origin. Coastal ancestry was associated with larger megalopae, even after accounting for temperature; however, temperature was a stronger predictor, with a standardised effect size more than three times greater than that of ancestry. A genome‐wide association study found no significant associations with megalopae size, suggesting the absence of a strong genotype–phenotype relationship or a lack of statistical power to detect a highly polygenic trait. Together with prior laboratory rearing studies, our findings support a dominant role for environmentally driven plasticity in body size variation. Persistent cohort differences previously observed in juvenile and adult body size raise the possibility that thermal conditions during early life may promote a carryover effect with potentially significant demographic and fishery implications.

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Predicting Aberrant Fc-fusion Protein Pharmacokinetics from In Silico Structural Properties and Physiologically Based Pharmacokinetic (PBPK) Modeling - Danilo Tomasoni; Alessio Paris; Roberto Visintainer; Kevin D. Cook; Aochiu Chen; Isabel Figueroa; Veena A. Thomas; Luca Marchetti (The AAPS Journal, 2026)
The fusion of therapeutic proteins to the Fc domain of monoclonal antibodies (mAbs) generally improves the proteins' pharmacokinetic (PK) characteristics, extending in vivo half-lives due to the binding of the Fc domain to the FcRn receptor. Yet, several of these Fc-fusion biologics have been observed to have unexpected rapid clearance associated with non-specific off-target binding. Variability in non-specific clearance is often challenging to predict, not well understood, and ultimately can delay the drug development process. In this investigation, we present a computational approach leveraging in silico protein structural properties to extend a physiologically based pharmacokinetic (PBPK) model of mAbs validated on in vivo plasma PK profiles in mice. Selected model parameters affecting protein half-life have been scaled by analytical functions of a panel of calculated in silico protein properties identified by a novel and ad hoc symbolic regression procedure. The resulting extended model has been successfully validated against an independent set of protein plasma PKs, indicating that it can generalize to novel biologics of the same class. Moreover, the extended PBPK model has a median absolute average fold error (AAFE) of 1.18 (min = 1.09; max = 1.51), where values less than 2 typically indicate a good fit. The results enable the de-risking of aberrant PK behaviors, ultimately leading to the selection of Fc-fusion proteins with increased therapeutic value for patients.

Western Bush Viper (Atheris chlorechis) Envenomation: A Case Report - Tyler F. Willing; Kenneth D. Katz; Matthew D. Cook; Lauren Augustine (Journal of Medical Toxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Leveraging additional VIIRS information to improve wildfire tracking in the western US - Shane R. Coffield; Tempest D. McCabe; Wilfrid Schroeder; Yang Chen; Rebecca C. Scholten; Elijah Orland; Tianjia Liu; Elizabeth Wiggins; James T. Randerson; Melanie Follette-Cook; Douglas C. Morton (Remote Sensing of Environment, 2026)

New Zealand blackcurrant extract has no effect on physiological and cardiovascular responses during low-intensity sustained intermittent isometric contractions in men - Stefano Montanari; Ben J. Lee; Sam D. Blacker; Matthew D. Cook; Mark E. T. Willems (European Journal of Applied Physiology, 2026)

FoScenes: A high-fidelity, large-scale 3D forest plant area density product derived from open-access airborne lidar data - Cailin Zhou; Tiangang Yin; Shanshan Wei; Bruce D. Cook; Weiwei Tan; Wai Yeung Yan; Qi Chen; Jean-Philippe Gastellu-Etchegorry (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Corrigendum to Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission Remote Sensing of Environment Volume 329, 1 November 2025, 114929 - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

Soybean genome‑wide association study of seed weight, protein, and oil content in the southeastern USA - Jinesh Patel; Sejal Patel; Lauren Cook; Benjamin D Fallen; Jenny Koebernick (Molecular Genetics and Genomics, 2025)
Soybean is a globally significant legume crop, providing essential protein and oil for human and livestock nutrition. Improving oil and protein content simultaneously without compromising yield has been challenging due to the quantitative nature of these traits and their interrelationships. This study aims to deepen our understanding of the molecular basis soybean of seed weight, protein, and oil content to facilitate marker-assisted breeding to enhance these traits. In this research, a Genome-Wide Association Study (GWAS) was conducted utilizing 285 diverse soybean accessions from maturity group V, employing genotyping through the SoySNP50K platform. These accessions were tested in three environmental conditions of the southeast US for three traits: 100-seed weight, protein, and oil content. The study identified 18, 23, and 26 SNPs significantly associated with 100-seed weight, seed oil, and protein content. Colocalized protein and oil content regions were discovered on chromosomes 15, 16, and 20. Chromosomes 15 and 20 are well documented to have pleiotropic but opposite effects on oil and protein content, but both regions contain genes that affect individual traits, such as FAD2-1 and nodulin MtN21. A 1.92 Mb region on chromosome 11 exhibits a target region to improve oil and seed weight without affecting protein content. This study highlights key genomic regions and candidate genes influencing seed weight, protein, and oil content, with some regions affecting multiple traits. Hence, these findings provide a valuable foundation for marker-assisted selection to optimize seed weight and simultaneously enhance oil and protein content in soybean breeding programs.

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

Insights from U.S. beekeeper triage surveys following unusually high honey bee colony losses 2024–2025 - Anthony Nearman; Christopher L. Crawford; M. Marta Guarna; Priyadarshini Chakrabarti; Katie Lee; Steven Cook; Elizabeth Hill; Arathi Seshadri; Garett Slater; Zachary S. Lamas; Yan Ping Chen; Danielle Downey; et al. (Science of The Total Environment, 2025)

Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

The state and fate of noble metals in bornite and digenite - Samuel A. King; Cristiana L. Ciobanu; Nigel J. Cook; Ashley D. Slattery; Sarah E. Gilbert; J. Richard Kyle; Kathy Ehrig; Jie Yao (Lithos, 2025)

Stakeholder values on the management of African elephants for large tree conservation in protected areas - Robin M. Cook; Ed T. F. Witkowski; Michelle D. Henley (European Journal of Wildlife Research, 2025)
Stakeholder perspectives play a crucial role in conservation decisions, particularly for species with complex ecological and social impacts, such as African savanna elephants ( Loxodonta africana ). In a South African protected area experiencing high elephant densities and significant tree loss, we surveyed 170 stakeholders, including conservation managers, property owners, tourists, and tourism personnel. Using a Likert scale and thematic analysis, we evaluated their attitudes towards tree protection, waterhole closures, contraception, and culling to mitigate elephant impacts on large trees. Results showed strong support for waterhole closures and tree protection, particularly among younger conservation managers and property owners, who viewed these methods as effective in dispersing elephant populations and safeguarding valuable trees. Conversely, tourists and younger stakeholders preferred non-lethal strategies like contraception, while conservation managers expressed practical concerns about its feasibility. Culling emerged as the most divisive strategy, supported primarily by older and male stakeholders in conservation but largely opposed by tourists due to ethical concerns. The chord diagram illustrated distinct patterns, with conservation managers aligning more with waterhole closures and culling, while property owners and tourists favoured tree protection and contraception. These findings highlight the diversity in stakeholder values, shaped by demographic factors, and underscore the need for adaptive, context-specific management strategies. Our study provides a framework for conservation policies that balance ecological objectives with social acceptability, promoting sustainable coexistence between elephants, large trees, and diverse stakeholder interests.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Rewetting alongside biochar and sulphate addition mitigates greenhouse gas emissions and retain carbon in degraded upland peatlands - Peduruhewa H. Jeewani; Robert W. Brown; Chris D. Evans; Jack Cook; Benjamin P. Roberts; Mariecia D. Fraser; David R. Chadwick; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Vertebral elemental composition reveals ontogenetic changes in habitat use in a Northeast Atlantic mesopredator shark - Neil D. Cook; Ana Samperiz; Morten Andersen; Edward Inglis; Marc-Alban Millet; Jo Cable; Sarah E. Perkins (Estuarine, Coastal and Shelf Science, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

DNA data (genome skims and metabarcodes) paired with chemical data demonstrate utility for retrospective analysis of forage linked to fatal poisoning of cattle - Daniel Cook; Brandon Kocurek; Clint Stonecipher; Kevin D. Welch; Dale R. Gardner; Mark Mammel; Elizabeth Reed; Padmini Ramachandran; David Erickson; Seth Commichaux; Andrea Ottesen (Toxicon, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The actions of varenicline on alkaloids from Conium maculatum (poison hemlock), Lupinus sulphureus (sulphur lupine) and Nicotiana glauca (tree tobacco) - Benedict T. Green; Stephen T. Lee; Kevin D. Welch; Daniel Cook; Clinton A. Stonecipher (Toxicon, 2024)

The evaluation of earwax as a noninvasive specimen to determine livestock exposure to death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Kevin D. Welch; Daniel Cook (Toxicon, 2024)

Mechanistic in silico explorations of the immunogenic and synergistic effects of radiotherapy and immunotherapy: a critical review - Allison M. Ng; Kelly M. MacKinnon; Alistair A. Cook; Rebecca A. D’Alonzo; Pejman Rowshanfarzad; Anna K. Nowak; Suki Gill; Martin A. Ebert (Physical and Engineering Sciences in Medicine, 2024)
Immunotherapy is a rapidly evolving field, with many models attempting to describe its impact on the immune system, especially when paired with radiotherapy. Tumor response to this combination involves a complex spatiotemporal dynamic which makes either clinical or pre-clinical in vivo investigation across the resulting extensive solution space extremely difficult. In this review, several in silico models of the interaction between radiotherapy, immunotherapy, and the patient’s immune system are examined. The study included only mathematical models published in English that investigated the effects of radiotherapy on the immune system, or the effect of immuno-radiotherapy with immune checkpoint inhibitors. The findings indicate that treatment efficacy was predicted to improve when both radiotherapy and immunotherapy were administered, compared to radiotherapy or immunotherapy alone. However, the models do not agree on the optimal schedule and fractionation of radiotherapy and immunotherapy. This corresponds to relevant clinical trials, which report an improved treatment efficacy with combination therapy, however, the optimal scheduling varies between clinical trials. This discrepancy between the models can be attributed to the variation in model approach and the specific cancer types modeled, making the determination of the optimum general treatment schedule and model challenging. Further research needs to be conducted with similar data sets to evaluate the best model and treatment schedule for a specific cancer type and stage.

Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Nature vs. nurture: Drivers of site productivity in loblolly pine (Pinus taeda L.) forests in the southeastern US - Vicent A. Ribas-Costa; Aitor Gastón; Sean A. Bloszies; Jesse D. Henderson; Andrew Trlica; David R. Carter; Rafael Rubilar; Timothy J. Albaugh; Rachel L. Cook (Forest Ecology and Management, 2024)

Avoidance and attraction responses of kittiwakes to three offshore wind farms in the North Sea - Christopher J. Pollock; Daniel T. Johnston; Philipp H. Boersch-Supan; Chris B. Thaxter; Elizabeth M. Humphreys; Nina J. O’Hanlon; Gary D. Clewley; Ewan D. Weston; Judy Shamoun-Baranes; Aonghais S. C. P. Cook (Marine Biology, 2024)
Seabird collision risk is a key concern in relation to the environmental impacts associated with offshore wind farms (OWFs). Understanding how species respond both to the wind farm itself, and individual turbines within the wind farm, is key to enabling better quantification and management of collision risk. Collision risk is of particular concern for the black-legged kittiwake, Rissa tridactyla , where modelling predicts unsustainable population level impacts. In this study 20 adult breeding kittiwakes, were tracked with GPS from Whinnyfold, Scotland (57°23′07″N, 001°52′11″W) during the breeding season in 2021. An Avoidance-Attraction Index (AAI) was estimated at several bands within macro- and meso-scales (0–4 km from outer boundary and 0–400 m from turbines, respectively), and the Avoidance Rate (AR; used in environmental impact assessments) at macro-scale to estimate avoidance behaviour to three operational OWFs within their foraging range. One offshore wind farm and its buffer zone (0–4 km from outer boundary) was visited more frequently by the majority of tracked individuals (19/20 birds), despite being twice as far as the closest OWF (17.3 and 31.9 km respectively), whilst 10 or less individuals used the remaining two OWFs. At the most frequented OWF we found macro-scale attraction to the closest band (0–1 km) trending towards avoidance in the furthest band (3–4 km). At the meso-scale we found avoidance of areas below the rotor height range (RHR, a.k.a. rotor swept area/zone) up to 120 m from individual turbines, which decreased to 60 m when within the RHR. Our results indicate that kittiwakes may be slightly attracted to the area around OWFs or aggregate here due to displacement but avoid individual turbines. Increased productivity in the OWF area may potentially be drawing birds into the general area, with aversion to individual turbines being responsible for meso-scale observations.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Temporal niche partitioning as a potential mechanism for coexistence in two sympatric mesopredator sharks - Neil D. Cook; Abbie Jenkins; Sarah L. Perry; Sarah E. Perkins; Jo Cable (Frontiers in Marine Science, 2024)
Global marine biodiversity declines require bold and ambitious plans to safeguard ecosystem services. Overfishing, habitat loss and projected climate impacts have yielded deleterious effects on marine predators, in particular, driving increasing threat of extinction for many shark species with implications for ecosystem health. Identifying and protecting critical habitat areas for sharks is fundamental to their protection, and may allow for species recovery. Here we use baited remote underwater video stations to investigate spatial and temporal patterns of habitat use by sharks in a Special Area of Conservation (SAC) that is centrally important to the regional blue economy in the UK, the Cardigan Bay SAC. Our results show heterogeneous spatial habitat use and temporal trends in habitat sharing between smallspotted catsharks Scyliorhinus canicula and nursehounds S. stellaris . Nearshore reef habitats are substantially more important than non-reef habitats for both species. The relative abundance of each species, however, is roughly inversely seasonally proportional, with S. canicula and S. stellaris relative abundance highest in March and September, respectively. Temporal niche partitioning may be an important mechanism in marine systems, but has not been widely investigated in sympatric shark communities. These findings are directly relevant for ongoing development of the Welsh Marine Evidence Strategy (2019-2025) and the Welsh National Marine Plan, particularly to inform spatial planning to strengthen the role of SAC management design in protecting important shark areas.

Influence of wind on kittiwake Rissa tridactyla flight and offshore wind turbine collision risk - Jacob G. Davies; Philipp H. Boersch-Supan; Gary D. Clewley; Elizabeth M. Humphreys; Nina J. O’Hanlon; Judy Shamoun-Baranes; Chris B. Thaxter; Ewan Weston; Aonghais S. C. P. Cook (Marine Biology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The use of earwax to determine livestock exposure to teratogenic lupine - Clinton A. Stonecipher; Stephen T. Lee; Kevin D. Welch; Kristian R. Valles; Daniel Cook (Toxicon, 2024)

Comparison of the acute toxicity of zygacine versus zygadenine - Kevin D. Welch; Dale R. Gardner; Stephen T. Lee; Clint A. Stonecipher; Daniel Cook (Toxicon, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

The value of seabird foraging ranges as a tool to investigate potential interactions with offshore wind farms - Ian D. Woodward; Chris B. Thaxter; Ellie Owen; Mark Bolton; Robin M. Ward; Aonghais S.C.P. Cook (Ocean & Coastal Management, 2024)

Reframing wildlife disease management problems with decision analysis - Margaret C. McEachran; Johanna A. Harvey; Riley O. Mummah; Molly C. Bletz; Claire S. Teitelbaum; Elias Rosenblatt; F. Javiera Rudolph; Fernando Arce; Shenglai Yin; Diann J. Prosser; Brittany A. Mosher; Jennifer M. Mullinax; et al. (Conservation Biology, 2024)
Contemporary wildlife disease management is complex because managers need to respond to a wide range of stakeholders, multiple uncertainties, and difficult trade‐offs that characterize the interconnected challenges of today. Despite general acknowledgment of these complexities, managing wildlife disease tends to be framed as a scientific problem, in which the major challenge is lack of knowledge. The complex and multifactorial process of decision‐making is collapsed into a scientific endeavor to reduce uncertainty. As a result, contemporary decision‐making may be oversimplified, rely on simple heuristics, and fail to account for the broader legal, social, and economic context in which the decisions are made. Concurrently, scientific research on wildlife disease may be distant from this decision context, resulting in information that may not be directly relevant to the pertinent management questions. We propose reframing wildlife disease management challenges as decision problems and addressing them with decision analytical tools to divide the complex problems into more cognitively manageable elements. In particular, structured decision‐making has the potential to improve the quality, rigor, and transparency of decisions about wildlife disease in a variety of systems. Examples of management of severe acute respiratory syndrome coronavirus 2, white‐nose syndrome, avian influenza, and chytridiomycosis illustrate the most common impediments to decision‐making, including competing objectives, risks, prediction uncertainty, and limited resources.

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Per- and polyfluoroalkyl substances (PFAS), perceived stress, and depressive symptoms in a prospective cohort study of black women - Samantha Schildroth; Birgit Claus Henn; Anissa I. Vines; Ruth J. Geller; Sharonda M. Lovett; Chad M. Coleman; Traci N. Bethea; Julianne Cook Botelho; Antonia M. Calafat; Chad Milando; Donna D. Baird; Ganesa Wegienka; et al. (Science of The Total Environment, 2024)

Acute death as a result of poisoning tropical (Bos taurus indicus) but not temperate (Bos taurus taurus) cattle after oral dosing with Lupinus leucophyllus (velvet lupine) - Benedict T. Green; Kevin D. Welch; Stephen T. Lee; T. Zane Davis; Clinton A. Stonecipher; Bryan L. Stegelmeier; Daniel Cook (Toxicon, 2024)

Deep learning of estuary salinity dynamics is physically accurate at a fraction of hydrodynamic model computational cost - Galen Gorski; Salme Cook; Amelia Snyder; Alison P. Appling; Theodore Thompson; Jared D. Smith; John C. Warner; Simon N. Topp (Limnology and Oceanography, 2024)
Salinity dynamics in the Delaware Bay estuary are a critical water quality concern as elevated salinity can damage infrastructure and threaten drinking water supplies. Current state‐of‐the‐art modeling approaches use hydrodynamic models, which can produce accurate results but are limited by significant computational costs. We developed a machine learning (ML) model to predict the 250 mg L −1 Cl − isochlor, also known as the “salt front,” using daily river discharge, meteorological drivers, and tidal water level data. We use the ML model to predict the location of the salt front, measured in river miles (RM) along the Delaware River, during the period 2001–2020, and we compare predictions of the ML model to the hydrodynamic Coupled Ocean–Atmosphere‐Wave‐Sediment Transport (COAWST) model. The ML model predicts the location of the salt front with greater accuracy (root mean squared error [RMSE] = 2.52 RM) than the COAWST model does (RMSE = 5.36); however, the ML model struggles to predict extreme events. Furthermore, we use functional performance and expected gradients, tools from information theory and explainable artificial intelligence, to show that the ML model learns physically realistic relationships between the salt front location and drivers (particularly discharge and tidal water level). These results demonstrate how an ML modeling approach can provide predictive and functional accuracy at a significantly reduced computational cost compared to process‐based models. In addition, these results provide support for using ML models in operational forecasting, scenario testing, management decisions, hindcasting, and resulting opportunities to understand past behavior and develop hypotheses.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Ruminant metabolism of zygacine, the major toxic alkaloid in foothill death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Benedict T. Green; Kevin D. Welch; Dale R. Gardner; Daniel Cook (Toxicon, 2024)

Variation in functional composition of reef fishes along a tropical‐to‐temperate gradient - Charlotte G. Clay; James D. Reimer; Brigitte Sommer; Katie M. Cook; Masaru Mizuyama; Masami Obuchi; Iori Kawamura; Hiroki Kise; Maria Beger (Journal of Biogeography, 2024)
Aims Transformation of species and functional composition on subtropical reefs are ongoing due to poleward range shifts of some tropical species, with largely unknown consequences to ecosystem functioning. Trait‐based approaches are powerful tools to quantify such changes. Here, we evaluated changes in the trait composition of coral‐associated fish assemblages along a tropical‐to‐temperate environmental gradient of ca. 1400 km in southern Japan with abundance‐weighted trait expression to assess how trait composition changes with increasing latitude. Location Ryukyu Islands and southern Pacific coast of Japan. Taxon Reef fish. Methods We tested for shifts in trait space and functional redundancy, based on five morphological, life history and behavioural traits: maximum length, pelagic larval duration, trophic level, substrate preference and reproductive mode. Our trait database was coded with two approaches, first, by attributing a single value to each trait per species, and second, by fuzzy coding that allows more than one value per trait and hence considers some intraspecific trait variation. Results We found a reduction in specialist habitat traits (coral substrate preference, nesters and herbivores) and an increase in generalist traits (predators) with increasing latitude, along with a contraction in trait space from tropical‐to‐temperate reefs. Functional redundancy declined with increasing latitude. These trends were closely linked with latitudinal gradients in temperature, along with changes in other environmental factors such as turbidity and photosynthetically active radiation. Main Conclusion Functional turnover and contractions are thus likely due to the marginal conditions for coral‐associated fishes at higher latitudes, favouring generalist species, whereas increased resources at lower latitudes favour high redundancy and niche partitioning. Accounting for intraspecific trait variation indicated the same trends but highlighted increased functional vulnerability across all sites. We show that trait complexity in coral‐associated fish communities decreases from tropical‐to‐temperate reefs, highlighting the reduced functional scope that comes with marginal environmental conditions.

The ectomycorrhizal fungus Paxillus ammoniavirescens influences the effects of salinity on loblolly pine in response to potassium availability - Benjamin D. Rose; Marissa A. Dellinger; Clancy P. Larmour; Mira I. Polishook; Maria I. Higuita‐Aguirre; Summi Dutta; Rachel L. Cook; Sabine D. Zimmermann; Kevin Garcia (Environmental Microbiology, 2024)
Salinity is an increasing problem in coastal areas affected by saltwater intrusion, with deleterious effects on tree health and forest growth. Ectomycorrhizal (ECM) fungi may improve the salinity tolerance of host trees, but the impact of external potassium (K + ) availability on these effects is still unclear. Here, we performed several experiments with the ECM fungus Paxillus ammoniavirescens and loblolly pine ( Pinus taeda L.) in axenic and symbiotic conditions at limited or sufficient K + and increasing sodium (Na + ) concentrations. Growth rate, biomass, nutrient content, and K + transporter expression levels were recorded for the fungus, and the colonization rate, root development parameters, biomass, and shoot nutrient accumulation were determined for mycorrhizal and non‐mycorrhizal plants. P. ammoniavirescens was tolerant to high salinity, although growth and nutrient concentrations varied with K + availability and increasing Na + exposure. While loblolly pine root growth and development decreased with increasing salinity, ECM colonization was unaffected by pine response to salinity. The mycorrhizal influence on loblolly pine salinity response was strongly dependent on external K + availability. This study reveals that P. ammoniavirescens can reduce Na + accumulation of salt‐exposed loblolly pine, but this effect depends on external K + availability.

Detailed characterisation of precious metals and critical elements in anode slimes from the Olympic Dam copper refinery, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Samuel A. King; Vanessa Liebezeit; Ashley D. Slattery (Minerals Engineering, 2024)

Visualization of radiographic mineral opacities in guinea pigs in the location of the bulbourethral glands may be underdiagnosed - Amanda D. Wong; Krista A. Keller; Anthony J. Cerreta; Kirstin Cook; Joanna K. Webb; Kenneth R. Welle; Martha A. Delaney; Audrey Billhymer (Journal of Exotic Pet Medicine, 2024)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (II) optimizing acquisition configurations - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Omar Regaieg; Zhijun Zhen; Rongjun Qin; et al. (Remote Sensing of Environment, 2023)

Modeling forest canopy surface retrievals using very high-resolution spaceborne stereogrammetry: (I) methods and comparisons with actual data - Tiangang Yin; Paul M. Montesano; Bruce D. Cook; Eric Chavanon; Christopher S.R. Neigh; David Shean; Dongju Peng; Nicolas Lauret; Ameni Mkaouar; Douglas C. Morton; Omar Regaieg; Zhijun Zhen; et al. (Remote Sensing of Environment, 2023)

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Unveiling the phenotypic landscape of stalk lodging resistance in diverse maize hybrids - Bharath Kunduru; Rohit Kumar; Manwinder S. Brar; Christopher J. Stubbs; Kaitlin Tabaracci; Norbert T. Bokros; William C. Bridges; Douglas D. Cook; Seth DeBolt; Christopher S. McMahan; Daniel J. Robertson; Rajandeep S. Sekhon (Field Crops Research, 2023)

Experimental evaluation of airflow guiding components for wind-driven single-sided natural ventilation: A comparative study in a test chamber - Nima Najafi Ziarani; Malcolm J. Cook; Paul D. O'Sullivan (Energy and Buildings, 2023)

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

Pb-bearing Cu-(Fe)-sulfides: Evidence for continuous hydrothermal activity in the northern Olympic Cu-Au Province, South Australia - Nicholas D. Owen; Nigel J. Cook; Rahul Ram; Joël Brugger; Roland Maas; Danielle S. Schmandt; Cristiana L. Ciobanu (Precambrian Research, 2023)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Feasibility and safety of synchrotron-based X-ray phase contrast imaging as a technique complementary to histopathology analysis - Kan Yan Chloe Li; Hector Dejea; Koen De Winne; Anne Bonnin; Valentino D’Onofrio; Janneke A. Cox; Patricia Garcia-Canadilla; Martin Lammens; Andrew C. Cook; Bart Bijnens; Amélie Dendooven (Histochemistry and Cell Biology, 2023)

Food biodiversity: Quantifying the unquantifiable in human diets - Giles T. Hanley-Cook; Aisling J. Daly; Roseline Remans; Andrew D. Jones; Kris A. Murray; Inge Huybrechts; Bernard De Baets; Carl Lachat (Critical Reviews in Food Science and Nutrition, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Survival trends (2008–2020) of three tree species in response to elephant impact, environmental variation, and stem wire-netting protection in an African savanna - Robin M. Cook; Ed T.F. Witkowski; Michelle D. Henley (Forest Ecology and Management, 2023)

Moving toward short stature maize: The effect of plant height on maize stalk lodging resistance - Christopher J. Stubbs; Bharath Kunduru; Norbert Bokros; Virginia Verges; Jordan Porter; Douglas D. Cook; Seth DeBolt; Christopher McMahan; Rajandeep S. Sekhon; Daniel J. Robertson (Field Crops Research, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

PCB126 exposure during pregnancy alters maternal and fetal gene expression - Cetewayo S. Rashid; Joshua D. Preston; Sara Y. Ngo Tenlep; Marissa K. Cook; Eric M. Blalock; Changcheng Zhou; Hollie I. Swanson; Kevin J. Pearson (Reproductive Toxicology, 2023)

Resiliency of Nuttall oak but not Shumard oak to winter and spring flood: dormancy alone does not confer flood tolerance - Richard D. Sample; James Cook; Benjamin A. Babst (Trees, 2023)

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa - Nikiwe Ndlovu; Frank H. Neumann; Michelle D. Henley; Robin M. Cook; Chevonne Reynolds (Palynology, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

The role of near-façade flow in wind-dominant single-sided natural ventilation for an isolated three-storey building: An LES study - Nima Najafi Ziarani; Malcolm J. Cook; Farnood Freidooni; Paul D. O'Sullivan (Building and Environment, 2023)

Quantifying the Effect Size of Management Actions on Aboveground Carbon Stocks in Forest Plantations - Cyril H. Melikov; Jacob J. Bukoski; Susan C. Cook-Patton; Hongyi Ban; Jessica L. Chen; Matthew D. Potts (Current Forestry Reports, 2023)
Purpose of the Review Improved forest management is a promising avenue for climate change mitigation. However, we lack synthetic understanding of how different management actions impact aboveground carbon stocks, particularly at scales relevant for designing and implementing forest-based climate solutions. Here, we quantitatively assess and review the impacts of three common practices—application of inorganic NPK fertilizer, interplanting with N-fixing species, and thinning—on aboveground carbon stocks in plantation forests. Recent Findings Site-level empirical studies show both positive and negative effects of inorganic fertilization, interplanting, and thinning on aboveground carbon stocks in plantation forests. Recent findings and the results of our analysis suggest that these effects are heavily moderated by factors such as species selection, precipitation, time since practice, soil moisture regime, and previous land use. Interplanting of N-fixing crops initially has no effect on carbon storage in main tree crops, but the effect becomes positive in older stands. Conversely, the application of NPK fertilizers increases aboveground carbon stocks, though the effect lessens with time. Moreover, increases in aboveground carbon stocks may be partially or completely offset by emissions from the application of inorganic fertilizer. Thinning results in a strong reduction of aboveground carbon stocks, though the effect lessens with time. Summary Management practices tend to have strong directional effects on aboveground carbon stocks in plantation forests but are moderated by site-specific management, climatic, and edaphic factors. The effect sizes quantified in our meta-analysis can serve as benchmarks for the design and scoping of improved forest management projects as forest-based climate solutions. Overall, management actions can enhance the climate mitigation potential of plantation forests, if performed with sufficient attention to the nuances of local conditions.

Total thermal neutron cross section measurements of hydrogen dense polymers from 0.0005–20 eV - D. Fritz; Y. Danon; K. Ramic; C.W. Chapman; J.M. Brown; G. Arbanas; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; P. Brain; A. Ney; et al. (Annals of Nuclear Energy, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV - D. Fritz; Y. Danon; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; C.W. Chapman; G. Arbanas; J.M. Brown; K. Ramic; X. Hu; S. Singh; et al. (Annals of Nuclear Energy, 2023)

Foresight science in conservation: Tools, barriers, and mainstreaming opportunities - Gabrielle Ednie; Tyreen Kapoor; Olga Koppel; Morgan L. Piczak; Jessica L. Reid; Alyssa D. Murdoch; Carly N. Cook; William J. Sutherland; Steven J. Cooke (Ambio, 2023)

The coupling of green and brown food webs regulates trophic position in a montane mammal guild - Philip J. Manlick; Joseph A. Cook; Seth D. Newsome (Ecology, 2023)
Food web ecology has revolutionized our understanding of ecological processes, but the drivers of food web properties like trophic position (TP) and food chain length are notoriously enigmatic. In terrestrial ecosystems, above‐ and belowground systems were historically compartmentalized into “green” and “brown” food webs, but the coupling of these systems by animal consumers is increasingly recognized, with potential consequences for trophic structure. We used stable isotope analysis (δ 13 C, δ 15 N) of individual amino acids to trace the flow of essential biomolecules and jointly measure multichannel feeding, food web coupling, and TP in a guild of small mammals. We then tested the hypothesis that brown energy fluxes to aboveground consumers increase terrestrial food chain length via cryptic trophic transfers during microbial decomposition. We found that the average small mammal consumer acquired nearly 70% of their essential amino acids (69.0% ± 7.6%) from brown food webs, leading to significant increases in TP across species and functional groups. Fungi were the primary conduit of brown energy to aboveground consumers, providing nearly half the amino acid budget for small mammals on average (44.3% ± 12.0%). These findings illustrate the tightly coupled nature of green and brown food webs and show that microbially mediated energy flow ultimately regulates food web structure in aboveground consumers. Consequently, we propose that the integration of green and brown energy channels is a cryptic driver of food chain length in terrestrial ecosystems.

Inconsistent results from trait-based analyses of moth trends point to complex drivers of change - George M. Tordoff; Emily B. Dennis; Richard Fox; Patrick M. Cook; Tony M. Davis; Dan Blumgart; Nigel A. D. Bourn (Biodiversity and Conservation, 2022)

Chemistry Manufacturing and Controls Development, Industry Reflections on Manufacture, and Supply of Pandemic Therapies and Vaccines - Matthew E. Popkin; Markus Goese; Diane Wilkinson; Stuart Finnie; Talia Flanagan; Cristiana Campa; Alexandra Clinch; Andrew Teasdale; Andrew Lennard; Graham Cook; Ganapathy Mohan; Matthew D. Osborne (The AAPS Journal, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

The physiological basis underlying functional connectivity differences in older adults: A multi-modal analysis of resting-state fMRI - Allen A. Champagne; Nicole S. Coverdale; Matti D. Allen; Joshua C. Tremblay; Rebecca E. K. MacPherson; Kyra E. Pyke; T. Dylan Olver; Douglas J. Cook (Brain Imaging and Behavior, 2022)

Resistance to amitraz in the parasitic honey bee mite Varroa destructor is associated with mutations in the β-adrenergic-like octopamine receptor - Carmen Sara Hernández-Rodríguez; Sara Moreno-Martí; Gabrielle Almecija; Krisztina Christmon; Josephine D. Johnson; Marie Ventelon; Dennis vanEngelsdorp; Steven C. Cook; Joel González-Cabrera (Journal of Pest Science, 2022)
Varroa destructor is considered a major reason for high loss rate of Western honey bee ( Apis mellifera ) colonies. To prevent colony losses caused by V. destructor, it is necessary to actively manage the mite population. Beekeepers, particularly commercial beekeepers, have few alternative treatments other than synthetic acaricides to control the parasite, resulting in intensive treatment regimens that led to the evolution of resistance in mite populations. To investigate the mechanism of the resistance to amitraz detected in V. destructor mites from French and U.S. apiaries, we identified and characterized octopamine and tyramine receptors (the known targets of amitraz) in this species. The comparison of sequences obtained from mites collected from different apiaries with different treatment regimens, showed that the amino acid substitutions N87S or Y215H in the OctβR were associated with treatment failures reported in French or U.S. apiaries, respectively. Based on our findings, we have developed and tested two high throughput diagnostic assays based on TaqMan technology able to accurately detect mites carrying the mutations in this receptor. This valuable information may be of help for beekeepers when selecting the most suitable acaricide to manage V. destructor .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Tracking the Rates and Mechanisms of Canopy Damage and Recovery Following Hurricane Maria Using Multitemporal Lidar Data - Veronika Leitold; Douglas C. Morton; Sebastián Martinuzzi; Ian Paynter; María Uriarte; Michael Keller; António Ferraz; Bruce D. Cook; Lawrence A. Corp; Grizelle González (Ecosystems, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Traits data for the butterflies and macro‐moths of Great Britain and Ireland - Patrick M. Cook; George M. Tordoff; Tony M. Davis; Mark S. Parsons; Emily B. Dennis; Richard Fox; Marc S. Botham; Nigel A. D. Bourn (Ecology, 2022)
Butterflies and moths, collectively Lepidoptera, are integral components of ecosystems, providing key services such as pollination and a prey resource for vertebrate and invertebrate predators. Lepidoptera are a relatively well studied group of invertebrates. In Great Britain and Ireland numerous citizen science projects provide data on changes in distribution and abundance. The availability of high‐quality monitoring and recording data, combined with the rapid response of Lepidoptera to environmental change, makes them ideal candidates for traits‐based ecological studies. Recently, there has been an increase in the number of studies documenting traits‐based responses of Lepidoptera, highlighting the demand for a standardized and referenced traits database. There is a wide range of primary and secondary literature sources available regarding the ecology of British and Irish Lepidoptera to support such studies. Currently these sources have not been collated into one central repository that would facilitate and enhance future research. Here, we present a comprehensive traits database for the butterflies and macro‐moths of Great Britain and Ireland. The database covers 968 species in 21 families. Ecological traits fall into four main categories: life cycle ecology and phenology, host plant specificity and characteristics, breeding habitat, and morphological characteristics. The database also contains data regarding species distribution, conservation status, and temporal trends for abundance and occupancy. This database can be used for a wide array of purposes including further fundamental research on species and community responses to environmental change, conservation and management studies, and evolutionary biology. There are no copyright restrictions, and this paper must be cited if data are used in publications.

Epiphytic fungal communities vary by substrate type and at submetre spatial scales - Kel Cook; Jyotsna Sharma; Andrew D. Taylor; Ian Herriott; D. Lee Taylor (Molecular Ecology, 2022)
Fungal species have numerous important environmental functions. Where these functions occur will depend on how fungi are spatially distributed, but the spatial structures of fungal communities are largely unknown, especially in understudied hyperdiverse tropical tree canopy systems. Here we explore fungal communities in a Costa Rican tropical rainforest canopy, with a focus on local‐scale spatial structure and substrate specificity of fungi. Samples of ~1 cm 3 were collected from 135 points along five adjacent tree branches, with intersample distances from 1 to 800 cm, and dissected into four substrates: outer host tree bark, inner bark, dead bryophytes and living bryophytes. We sequenced the ITS2 region to characterize total fungal communities. Fungal community composition and diversity varied among substrate types, even when multiple substrates were in direct contact. Fungi were most diverse in living bryophytes, with 39% of all operational taxonomic units (OTUs) found exclusively in this substrate, and the least diverse in inner bark. Fungal communities had significant positive spatial autocorrelation and distance decay of similarity only at distances less than 1 m. Similarity among samples declined by half in less than 10 cm, and even at these short distances, similarities were low with few OTUs shared among samples. These results indicate that community turnover is high and occurs at very small spatial scales, with any two locations sharing very few fungi in common. High heterogeneity of fungal communities in space and among substrates may have implications for the distributions, population dynamics and diversity of other tree canopy organisms, including epiphytic plants.

Prioritization and thresholds for managing biological invasions in urban ecosystems - L. J. Potgieter; M. F. J. Aronson; A. J. Brandt; C. N. Cook; M. Gaertner; N. E. Mandrak; D. M. Richardson; N. Shrestha; M. W. Cadotte (Urban Ecosystems, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Detection of Hepatitis A Virus in Strawberries Implicated in an Outbreak in the USA in 1997 - N. Cook; L. Vickers-Smith; M. D’Agostino (Food and Environmental Virology, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Novel Application of Photogrammetry to Quantify Fascicle Orientations of Female Cadaveric Pelvic Floor Muscles - Megan R. Routzong; Mark S. Cook; William Barone; Steven D. Abramowitch; Marianna Alperin (Annals of Biomedical Engineering, 2021)

Synergistic antihyperalgesic and antinociceptive effects of morphine and methyl 8-ethynyl-6-(pyridin-2-yl)-4H-benzo[f]imidazo[1,5-a][1,4]diazepine-3-carboxylate (MP-III-024): a positive allosteric modulator at α2GABAA and α3GABAA receptors - Mohammad A. Rahman; Thomas M. Keck; Michael M. Poe; Dishary Sharmin; James M. Cook; Bradford D. Fischer (Psychopharmacology, 2021)

Corrigendum to: The global Microcystis interactome - K.V. Cook; C. Li; H. Cai; L.R. Krumholz; K.D. Hambright; H.W. Paerl; M.M. Steffen; A.E. Wilson; M.A. Burford; H.‐P. Grossart; D. P. Hamilton; H. Jiang; et al. (Limnology and Oceanography, 2021)

The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Ali H. Abdulhussain; Kathryn B. Cook; Andrew D. Turner; Adam M. Lewis; Thomas S. Bibby; Daniel J. Mayor (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense ), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa . Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella , a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100% mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella . Animals offered 1,000 μg C L –1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 μg C L –1 . The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Visualisation of cholesterol and ganglioside GM1 in zebrafish models of Niemann–Pick type C disease and Smith–Lemli–Opitz syndrome using light sheet microscopy - Sophie R. Cook; Cerys Bladen; Johanna Smith; Emily Maguire; Jordan Copner; Gareth D. Fenn; Kim Wager; Helen Waller-Evans; Emyr Lloyd-Evans (Histochemistry and Cell Biology, 2020)
Lysosomal storage diseases are the most common cause of neurodegeneration in children. They are characterised at the cellular level by the accumulation of storage material within lysosomes. There are very limited therapeutic options, and the search for novel therapies has been hampered as few good small animal models are available. Here, we describe the use of light sheet microscopy to assess lipid storage in drug and morpholino induced zebrafish models of two diseases of cholesterol homeostasis with lysosomal dysfunction: First, Niemann–Pick type C disease (NPC), caused by mutations in the lysosomal transmembrane protein NPC1, characterised by intralysosomal accumulation of cholesterol and several other lipids. Second, Smith–Lemli–Opitz syndrome (SLOS), caused by mutations in 7-dehydrocholesterol reductase, which catalyses the last step of cholesterol biosynthesis and is characterised by intralysosomal accumulation of dietary cholesterol. This is the first description of a zebrafish SLOS model. We find that zebrafish accurately model lysosomal storage and disease-specific phenotypes in both diseases. Increased cholesterol and ganglioside GM1 were observed in sections taken from NPC model fish, and decreased cholesterol in SLOS model fish, but these are of limited value as resolution is poor, and accurate anatomical comparisons difficult. Using light sheet microscopy, we were able to observe lipid changes in much greater detail and identified an unexpected accumulation of ganglioside GM1 in SLOS model fish. Our data demonstrate, for the first time in zebrafish, the immense potential that light sheet microscopy has in aiding the resolution of studies involving lysosomal and lipid disorders.

Regional environmental drivers of Kemp’s ridley sea turtle somatic growth variation - Matthew D. Ramirez; Larisa Avens; Lisa R. Goshe; Melissa L. Snover; Melissa Cook; Heather L. Haas; Selina S. Heppell (Marine Biology, 2020)

Sex Differences in Pediatric Poisonings by Age Group: a Toxicology Investigators’ Consortium (ToxIC) Analysis (2010–2016) - Gillian A. Beauchamp; Jennifer L. Carey; Matthew D. Cook; Robert D. Cannon; Kenneth D. Katz; Jennifer Yoon; Hope Kincaid; Brittany J. Ely; Emily Pollack; Richard J. Mazzaccaro; Marna Rayl Greenberg (Journal of Medical Toxicology, 2020)

Biosecurity policy and legislation for the global seaweed aquaculture industry - Iona Campbell; Cicilia S. B. Kambey; Jonalyn P. Mateo; Sadock B. Rusekwa; Anicia Q. Hurtado; Flower E. Msuya; Grant D. Stentiford; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Each year a significant proportion of global food production is lost to pests and diseases, with concerted efforts by government and industry focussed on application of effective biosecurity policies which attempt to minimise their emergence and spread. In aquaculture the volume of seaweeds produced is second only to farmed fish and red algal carrageenophytes currently represent approximately 42% of global production of all seaweeds. Despite this importance, expansion of the seaweed sector is increasingly limited by the high prevalence of recalcitrant diseases and epiphytic pests with potential to emerge and with the demonstrated propensity to spread, particularly in the absence of effective national and international biosecurity policies. Developing biosecurity policy and legislation to manage biosecurity risk in seaweed aquaculture is urgently required to limit these impacts. To understand current international biosecurity frameworks and their efficacy, existing legislative frameworks were analysed quantitatively for the content of biosecurity measures, applicability to the seaweed industry, and inclusion of risks posed by diseases, pests and non-native species. Deficiencies in existing frameworks included the following: inconsistent terminology for inclusion of cultivated seaweeds, unclear designation of implementation responsibility, insufficient evidence-based information and limited alignment of biosecurity hazards and risks. Given the global importance of the cultivation of various seaweeds in alleviating poverty in low and middle income countries, it is crucial that the relatively low-unit value of the industry (i.e. as compared with other aquatic animal sectors) should not conflate with a perceived low risk of disease or pest transfer, nor the subsequent economic and environmental impact that disease transfer may impact on receiving nations (well beyond their seaweed operations). Developing a clear basis for development of robust international biosecurity policies related to the trade in seaweeds arising from the global aquaculture industry, by first addressing the gaps highlighted in this study, will be crucial in limiting impacts of pests and diseases on this valuable industry and on natural capital in locations where seaweeds are farmed.

Tree diversity promotes growth of late successional species despite increasing deer damage in a restored forest - John L. Devaney; Jamie Pullen; Susan C. Cook‐Patton; Karin T. Burghardt; John D. Parker (Ecology, 2020)
The role of tree diversity in restored forests and its impact on key ecological processes like growth and resistance to herbivory has become increasingly important. We analyzed height growth and white‐tailed deer Odocoileus virginianus browsing damage to saplings of 16 broadleaved tree species in a large‐scale (13 ha) reforestation experiment in Maryland, USA, where we manipulated tree diversity in 70 1,225‐m 2 plots. After four growing seasons, higher plot‐level tree richness led to increased deer browsing damage (i.e., associational susceptibility). Despite increased deer damage to saplings in mixed plots, tree richness had no overall effect on sapling height growth. However, diversity–height relationships were related to species functional traits. Light demanding species with large leaves and faster growth rates had reduced heights in mixtures, whereas shade‐tolerant, slower‐growing species generally had either increased or unchanged height growth in diverse tree communities, likely related to increased canopy closure in mixtures relative to monocultures. We show that tree diversity can improve growth of late successional species despite exacerbated mammalian herbivore damage. By facilitating the establishment of species with a range of life‐history strategies, increased tree diversity may enhance ecosystem multi‐functionality in the early stages of forest restoration.

Simulating alternative sustainable water futures - D. A. Sampson; E. M. Cook; M. J. Davidson; N. B. Grimm; D. M. Iwaniec (Sustainability Science, 2020)

Regional Variation in Kemp’s Ridley Sea Turtle Diet Composition and Its Potential Relationship With Somatic Growth - Matthew D. Ramirez; Larisa Avens; Lisa R. Goshe; Melissa L. Snover; Melissa Cook; Selina S. Heppell (Frontiers in Marine Science, 2020)

Resilience of pond communities to extreme thermal regime shifts: an alpine–montane reciprocal transplant experiment - Mitchell A. Johnsen; Blake R. Stuparyk; Jenna Cook; Rolf D. Vinebrooke (Aquatic Sciences, 2020)

The Vertical and Horizontal Distribution of Deep-Sea Crustaceans in the Order Euphausiacea in the Vicinity of the DeepWater Horizon Oil Spill - Tamara M. Frank; Charles D. Fine; Eric A. Burdett; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

Ultra-endurance triathlon performance and markers of whole-body and gut-specific inflammation - Kyle A. Smith; Jacob N. Kisiolek; Brandon D. Willingham; Margaret C. Morrissey; Samantha M. Leyh; Patrick G. Saracino; Daniel A. Baur; Marc D. Cook; Michael J. Ormsbee (European Journal of Applied Physiology, 2020)

Concordance of chemically inferred and assayed nutrient limitation of phytoplankton along a depth gradient of alpine lakes in the Canadian Rockies - Jenna Cook; Blake R. Stuparyk; Mitchell A. Johnsen; Rolf D. Vinebrooke (Aquatic Sciences, 2020)

Orchid fleck virus associated with the first case of citrus leprosis-N in South Africa - Glynnis Cook; Wayne Kirkman; Rochelle Clase; Chanel Steyn; Elaine Basson; Paul H. Fourie; Sean D. Moore; Tim G. Grout; Elma Carstens; Vaughan Hattingh (European Journal of Plant Pathology, 2019)

A fluvially derived flood deposit dating to the Kamikaze typhoons near Nagasaki, Japan - Caroline Ladlow; Jonathan D. Woodruff; Timothy L. Cook; Hannah Baranes; Kinuyo Kanamaru (Natural Hazards, 2019)

Improving conservation practice with principles and tools from systems thinking and evaluation - Andrew T. Knight; Carly N. Cook; Kent H. Redford; Duan Biggs; Claudia Romero; Alejandro Ortega-Argueta; Cameron D. Norman; Beverly Parsons; Martin Reynolds; Glenda Eoyang; Matt Keene (Sustainability Science, 2019)

Adverse Drug Events and Reactions Managed by Medical Toxicologists: an Analysis of the Toxicology Investigators Consortium (ToxIC) Registry, 2010–2016 - Gillian A. Beauchamp; Alexandra Amaducci; Marna Rayl Greenberg; Matthew Meyers; Matthew Cook; Robert D. Cannon; Kenneth D. Katz; Yaron Finkelstein (Journal of Medical Toxicology, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

3D Printing of Metformin HCl PVA Tablets by Fused Deposition Modeling: Drug Loading, Tablet Design, and Dissolution Studies - Mariam Ibrahim; Morgan Barnes; Robert McMillin; Daniel W. Cook; Sarah Smith; Mathew Halquist; Dayanjan Wijesinghe; Thomas D. Roper (AAPS PharmSciTech, 2019)

Utility of the Compensatory Tracking Task for Objective Differentiation of Hypersomnolence in Depression: A High-Density EEG Investigation - Emily C. Forscher; Michael L. Prairie; Jesse D. Cook; Sydney L. Notermann; David T. Plante (Sleep and Vigilance, 2019)

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

The Influence of Human Demography on Land Cover Change in the Great Lakes States, USA - Mark J. Ducey; Kenneth M. Johnson; Ethan P. Belair; Barbara D. Cook (Environmental Management, 2018)

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

An ancient and a recent colonization of islands by an Australian sap‐feeding insect - Caroline Fromont; Paul D. Rymer; Markus Riegler; James M. Cook (Journal of Biogeography, 2018)
Aim To assess the genetic structure, biogeography, and the potential for speciation, of a highly host‐specific insect pest with mainland and island populations. Location East coast of Australia, Lord Howe Island ( LHI ), and New Zealand. Methods We focussed on Mycopsylla fici , a plant sap‐feeding insect host‐specific to the fig tree Ficus macrophylla . We genotyped 152 insects from across the natural and extended host plant range at 14 microsatellite loci and analysed the data using standard population genetics statistics, Discriminant Analysis of Principal Components, genetic autocorrelation, and two Bayesian clustering approaches. Results Genetic analyses revealed that the northeastern Australian mainland population (Brisbane) is the centre of genetic diversity. Northeastern and southeastern (Sydney) mainland populations are genetically differentiated and interconnected in a stepping‐stone pattern. The LHI population is the most distinct genetically and Bayesian estimates indicated that the most recent colonization occurred c . 2,000‐17,500 years ago from a northeastern mainland origin. In contrast, the New Zealand population is little differentiated from the Sydney population and probably diverged by colonization within the past 200 years. Main conclusions The strong differentiation in nuclear microsatellites mirrors previous evidence for divergence of the LHI population from both mt DNA and endosymbiont DNA . The LHI population may be undergoing speciation from the mainland populations, with an oceanic barrier to gene flow. In contrast, the geographically isolated population in Auckland represents a far more recent colonization reflecting the contemporary naturalization of the plant host in New Zealand.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

An economic assessment of the impact on the Western Australian viticulture industry from the incursion of grapevine downy mildew - A. S. Taylor; D. C. Cook (Journal of Plant Diseases and Protection, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Examining olfactory and visual cues governing host-specificity of a weed biological control candidate species to refine pre-release risk assessment - Ikju Park; Sanford D. Eigenbrode; Stephen P. Cook; Bradley L. Harmon; Hariet L. Hinz; Urs Schaffner; Mark Schwarzländer (BioControl, 2018)

Trends of two HPV-associated cancers in Massachusetts: cervical and oropharyngeal cancer - Erin E. Cook; Susan T. Gershman; Jane J. Kim; Rulla M. Tamimi; R. Monina Klevens; Michelle D. Holmes (Cancer Causes & Control, 2018)

Effects of group size on school structure and behaviour in yellow‐eyed mullet Aldrichetta forsteri - K. L. Middlemiss; D. G. Cook; A. R. Jerrett; W. Davison (Journal of Fish Biology, 2018)
Schooling behaviour in yellow‐eyed mullet Aldrichetta forsteri , a common fish species in New Zealand estuarine habitats, was investigated to identify interaction rules associated with group formation. Tank‐based three‐dimensional studies of three group sizes (15, 75 and 150 individuals) were carried out to measure the effects of these different group sizes on school structure during control, predation risk and foraging behavioural states. Increased group size positively correlated with nearest‐neighbour distance in control and foraging states. Swimming speed was the lowest in all three behavioural states in groups of 15 fish compared with 75 or 150. Immediate behavioural response following visual exposure to a simulated avian predator differed between groups resulting in loss of structure in larger groups. School shape was an oblong–oblate spheroid with a length, breadth and height ratio of 5:2:1 and the area of free space surrounding individual fish was spherical in shape with a high degree of spatial isotropy present in all size groups. These findings challenge traditional theories based on either local or global properties as key drivers of group structure. Instead, our results suggest that a more collaborative approach involving both group size and rules pertaining to nearest‐neighbour interactions affects collective behaviours in this species.

Negative allosteric modulation of alpha 5-containing GABAA receptors engenders antidepressant-like effects and selectively prevents age-associated hyperactivity in tau-depositing mice - Nina Z. Xu; Margot Ernst; Marco Treven; Rok Cerne; Mark Wakulchik; Xia Li; Timothy M. Jones; Scott D. Gleason; Denise Morrow; Jeffrey M. Schkeryantz; Md. Toufiqur Rahman; Guanguan Li; et al. (Psychopharmacology, 2018)

Coagulase-negative staphylococci are associated to the mild inflammatory pattern of healthcare-associated meningitis: a retrospective study - S. Couffin; D. Lobo; F. Cook; P. H. Jost; V. Bitot; R. Birnbaum; B. Nebbad; B. Aït-Mamar; W. Lahiani; M. Martin; G. Dhonneur; R. Mounier (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Agro-morphological traits of Cicer reticulatum Ladizinsky in comparison to C. echinospermum P.H. Davis in terms of potential to improve cultivated chickpea (C. arietinum L.) - Mirlan Talip; Alper Adak; Abdullah Kahraman; Jens Berger; Duygu Sari; Hatice Sari; R. V. Penmetsa; E. J. von Wettberg; D. R. Cook; Cengiz Toker (Genetic Resources and Crop Evolution, 2018)

Survival estimates for the greater crested tern Thalasseus bergii in southern Africa - A Payo-Payo; A Sanz-Aguilar; D Gaglio; RB Sherley; TR Cook; R Altwegg; PG Ryan (African Journal of Marine Science, 2018)

Factors affecting distribution and abundance of jellyfish medusae in a temperate estuary: a multi-decadal study - Jason Baumsteiger; Teejay A. O’Rear; Jonathan D. Cook; Amber D. Manfree; Peter B. Moyle (Biological Invasions, 2018)

Potential Approaches to Assess the Infectivity of Hepatitis E Virus in Pork Products: A Review - Nigel Cook; Martin D’Agostino; Reimar Johne (Food and Environmental Virology, 2017)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Qualifying and quantifying minimal hepatic encephalopathy - Marsha Y. Morgan; Piero Amodio; Nicola A. Cook; Clive D. Jackson; Gerald Kircheis; Mette M. Lauridsen; Sara Montagnese; Sami Schiff; Karin Weissenborn (Metabolic Brain Disease, 2016)

Metabolome‐mediated biocryomorphic evolution promotes carbon fixation in G reenlandic cryoconite holes - Joseph M. Cook; Arwyn Edwards; Mark Bulling; Luis A. J. Mur; Sophie Cook; Jarishma K. Gokul; Karen A. Cameron; Michael Sweet; Tristram D. L. Irvine‐Fynn (Environmental Microbiology, 2016)
Summary Microbial photoautotrophs on glaciers engineer the formation of granular microbial‐mineral aggregates termed cryoconite which accelerate ice melt, creating quasi‐cylindrical pits called ‘cryoconite holes’. These act as biogeochemical reactors on the ice surface and provide habitats for remarkably active and diverse microbiota. Evolution of cryoconite holes towards an equilibrium depth is well known, yet interactions between microbial activity and hole morphology are currently weakly addressed. Here, we experimentally perturbed the depths and diameters of cryoconite holes on the Greenland Ice Sheet. Cryoconite holes responded by sensitively adjusting their shapes in three dimensions (‘biocryomorphic evolution’) thus maintaining favourable conditions for net autotrophy at the hole floors. Non‐targeted metabolomics reveals concomitant shifts in cyclic AMP and fucose metabolism consistent with phototaxis and extracellular polymer synthesis indicating metabolomic‐level granular changes in response to perturbation. We present a conceptual model explaining this process and suggest that it results in remarkably robust net autotrophy on the Greenland Ice Sheet. We also describe observations of cryoconite migrating away from shade, implying a degree of self‐regulation of carbon budgets over mesoscales. Since cryoconite is a microbe‐mineral aggregate, it appears that microbial processes themselves form and maintain stable autotrophic habitats on the surface of the Greenland ice sheet.

Sedimentological records of the C.E. 1707 Hōei Nankai Trough tsunami in the Bungo Channel, southwestern Japan - Hannah E. Baranes; Jonathan D. Woodruff; Davin J. Wallace; Kinuyo Kanamaru; Timothy L. Cook (Natural Hazards, 2016)

Cape cormorants decrease, move east and adapt foraging strategies following eastward displacement of their main prey - RJM Crawford; RM Randall; TR Cook; PG Ryan; BM Dyer; R Fox; D Geldenhuys; J Huisamen; C McGeorge; MK Smith; L Upfold; J Visagie; et al. (African Journal of Marine Science, 2016)

Effects of a common transcranial direct current stimulation (tDCS) protocol on motor evoked potentials found to be highly variable within individuals over 9 testing sessions - Jared Cooney Horvath; Simon J. Vogrin; Olivia Carter; Mark J. Cook; Jason D. Forte (Experimental Brain Research, 2016)

Colistin combination therapy improves microbiologic cure in critically ill patients with multi-drug resistant gram-negative pneumonia - N. L. Parchem; K. A. Bauer; C. H. Cook; J. E. Mangino; C. D. Jones; K. Porter; C. V. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Flood risk management, an approach to managing cross-border hazards - L. J. Bracken; E. A. Oughton; A. Donaldson; B. Cook; J. Forrester; C. Spray; S. Cinderby; D. Passmore; N. Bissett (Natural Hazards, 2016)

Association of gold with uraninite and pyrobitumen in the metavolcanic rock hosted hydrothermal Au-U mineralisation at Rompas, Peräpohja Schist Belt, northern Finland - Ferenc Molnár; Harry Oduro; Nick D. J. Cook; Esa Pohjolainen; Ágnes Takács; Hugh O’Brien; Lassi Pakkanen; Bo Johanson; Richard Wirth (Mineralium Deposita, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Much more give than take: South Africa as a major donor but infrequent recipient of invasive non‐native grasses - Vernon Visser; John R. U. Wilson; Lyn Fish; Carly Brown; Garry D. Cook; David M. Richardson (Global Ecology and Biogeography, 2016)
Aim Some regions donate more invaders from particular taxonomic and functional groups than they receive. We demonstrate a particularly striking donor–recipient asymmetry in invasion ecology in grasses. Specifically, we explore whether low numbers of invasive grasses in South Africa can be explained by sampling biases, introduction dynamics, species traits or invasibility of ecosystems. Location South Africa, Australia, Chile, Europe and the USA. Methods We tested for a donor–recipient asymmetry using lists of native and non‐native grasses in five regions across the globe. Then, using distribution, trait and environmental data, we tested whether regions differed in: (1) herbarium sampling effort; (2) introduction dynamics of non‐native grasses (primary uses, area of origin and minimum residence time of non‐native grasses); (3) traits of native and non‐native grasses (leaf size, height, life history, growth form, C 3 :C 4 ratio and taxonomic placement); and (4) fire frequency. Results South Africa has fewer invasive grasses, and fewer widespread invasive grasses, than other regions; while grasses native to South Africa are much more likely to be invasive elsewhere than other grasses. This asymmetry cannot be explained by sampling biases, historical trade links or minimum residence time. Rather it is likely to be due to a combination of: (1) the massive scale of the introduction of South African grasses around the world; (2) specific traits that make South African grasses successful competitors; and (3) the high fire frequency of many South African ecosystems to which many native grasses are adapted, but introduced grasses are not. Main conclusion South Africa has a high diversity of grasses that possess specific traits to cope with fire, grazing and disturbance. This makes them more competitive. Moreover, the high diversity of certain grass lineages in South Africa acts as a reservoir of potential invaders and possibly helps limit invasions in South Africa by promoting fire.

Larvae influence thermoregulatory fanning behavior in honeybees (Apis mellifera L.) - C. N. Cook; S. Durzi; K. J. Scheckel; M. D. Breed (Insectes Sociaux, 2016)

Monitoring of Extraction Efficiency by a Sample Process Control Virus Added Immediately Upon Sample Receipt - Vurayai Ruhanya; Marta Diez-Valcarce; Martin D’Agostino; Nigel Cook; Marta Hernández; David Rodríguez-Lázaro (Food and Environmental Virology, 2015)

Buffel grass and climate change: a framework for projecting invasive species distributions when data are scarce - Tara G. Martin; Helen Murphy; Adam Liedloff; Colette Thomas; Iadine Chadès; Garry Cook; Rod Fensham; John McIvor; Rieks D. van Klinken (Biological Invasions, 2015)

Antidepressant treatment history and drug-placebo separation in a placebo-controlled trial in major depressive disorder - Aimee M. Hunter; Ian A. Cook; Molly Tartter; Simi K. Sharma; Gregory D. Disse; Andrew F. Leuchter (Psychopharmacology, 2015)

Natural abundance (δ15N) indicates shifts in nitrogen relations of woody taxa along a savanna–woodland continental rainfall gradient - Fiona M. Soper; Anna E. Richards; Ilyas Siddique; Marcos P. M. Aidar; Garry D. Cook; Lindsay B. Hutley; Nicole Robinson; Susanne Schmidt (Oecologia, 2015)

Integrating physiological threshold experiments with climate modeling to project mangrove species’ range expansion - Kyle C. Cavanaugh; John D. Parker; Susan C. Cook‐Patton; Ilka C. Feller; A. Park Williams; James R. Kellner (Global Change Biology, 2015)
Predictions of climate‐related shifts in species ranges have largely been based on correlative models. Due to limitations of these models, there is a need for more integration of experimental approaches when studying impacts of climate change on species distributions. Here, we used controlled experiments to identify physiological thresholds that control poleward range limits of three species of mangroves found in North America. We found that all three species exhibited a threshold response to extreme cold, but freeze tolerance thresholds varied among species. From these experiments, we developed a climate metric, freeze degree days ( FDD ), which incorporates both the intensity and the frequency of freezes. When included in distribution models, FDD accurately predicted mangrove presence/absence. Using 28 years of satellite imagery, we linked FDD to observed changes in mangrove abundance in Florida, further exemplifying the importance of extreme cold. We then used downscaled climate projections of FDD to project that these range limits will move northward by 2.2–3.2 km yr −1 over the next 50 years.

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

Occupational exposure and ovarian cancer risk - Nhu D. Le; Andy Leung; Angela Brooks-Wilson; Richard P. Gallagher; Kenneth D. Swenerton; Paul A. Demers; Linda S. Cook (Cancer Causes & Control, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Processes and Drivers of Nitrogen Removal in Stormwater Biofiltration - Emily G. I. Payne; Tim D. Fletcher; Perran L. M. Cook; Ana Deletic; Belinda E. Hatt (Critical Reviews in Environmental Science and Technology, 2014)

The number of days on which increment occurs is the primary determinant of annual ring width in Callitris intratropica - David M. Drew; Anna E. Richards; Garry D. Cook; Geoffrey M. Downes; Warwick Gill; Patrick J. Baker (Trees, 2014)

Colony social structure in native and invasive populations of the social wasp Vespula pensylvanica - Cause Hanna; Erin D. Cook; Ariel R. Thompson; Lyndzey E. Dare; Amanda L. Palaski; David Foote; Michael A. D. Goodisman (Biological Invasions, 2014)

Estimating the Cost and Carbon Impact of a Long Term Water Main Rehabilitation Strategy - D. J. Beale; D. R. Marlow; S. Cook (Water Resources Management, 2013)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

Arboreal thorn-dwelling ants coexisting on the savannah ant-plant, Vachellia erioloba, use domatia morphology to select nest sites - H. Campbell; M. D. E. Fellowes; J. M. Cook (Insectes Sociaux, 2013)

Linking anti‐predator behaviour to prey demography reveals limited risk effects of an actively hunting large carnivore - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; Michael D. Jimenez; Rachel C. Cook; John G. Cook; Shannon E. Albeke; Hall Sawyer; P. J. White (Ecology Letters, 2013)
Ecological theory predicts that the diffuse risk cues generated by wide‐ranging, active predators should induce prey behavioural responses but not major, population‐ or community‐level consequences. We evaluated the non‐consumptive effects ( NCE s) of an active predator, the grey wolf ( Canis lupus ), by simultaneously tracking wolves and the behaviour, body fat, and pregnancy of elk ( Cervus elaphus ), their primary prey in the Greater Yellowstone Ecosystem. When wolves approached within 1 km, elk increased their rates of movement, displacement and vigilance. Even in high‐risk areas, however, these encounters occurred only once every 9 days. Ultimately, despite 20‐fold variation in the frequency of encounters between wolves and individual elk, the risk of predation was not associated with elk body fat or pregnancy. Our findings suggest that the ecological consequences of actively hunting large carnivores, such as the wolf, are more likely transmitted by consumptive effects on prey survival than NCE s on prey behaviour.

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

Rejoinder: challenge and opportunity in the study of ungulate migration amid environmental change - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)

Animal migration amid shifting patterns of phenology and predation: lessons from a Yellowstone elk herd - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)
Migration is a striking behavioral strategy by which many animals enhance resource acquisition while reducing predation risk. Historically, the demographic benefits of such movements made migration common, but in many taxa the phenomenon is considered globally threatened. Here we describe a long‐term decline in the productivity of elk ( Cervus elaphus ) that migrate through intact wilderness areas to protected summer ranges inside Yellowstone National Park, USA. We attribute this decline to a long‐term reduction in the demographic benefits that ungulates typically gain from migration. Among migratory elk, we observed a 21‐year, 70% reduction in recruitment and a 4‐year, 19% depression in their pregnancy rate largely caused by infrequent reproduction of females that were young or lactating. In contrast, among resident elk, we have recently observed increasing recruitment and a high rate of pregnancy. Landscape‐level changes in habitat quality and predation appear to be responsible for the declining productivity of Yellowstone migrants. From 1989 to 2009, migratory elk experienced an increasing rate and shorter duration of green‐up coincident with warmer spring–summer temperatures and reduced spring precipitation, also consistent with observations of an unusually severe drought in the region. Migrants are also now exposed to four times as many grizzly bears ( Ursus arctos ) and wolves ( Canis lupus ) as resident elk. Both of these restored predators consume migratory elk calves at high rates in the Yellowstone wilderness but are maintained at low densities via lethal management and human disturbance in the year‐round habitats of resident elk. Our findings suggest that large‐carnivore recovery and drought, operating simultaneously along an elevation gradient, have disproportionately influenced the demography of migratory elk. Many migratory animals travel large geographic distances between their seasonal ranges. Changes in land use and climate that disparately influence such seasonal ranges may alter the ecological basis of migratory behavior, representing an important challenge for, and a powerful lens into, the ecology and conservation of migratory taxa.

Role of gamma-aminobutyric acid type A (GABAA) receptor subtypes in acute benzodiazepine physical dependence-like effects: evidence from squirrel monkeys responding under a schedule of food presentation - Bradford D. Fischer; Laura P. Teixeira; Michael L. van Linn; Ojas A. Namjoshi; James M. Cook; James K. Rowlett (Psychopharmacology, 2013)

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Stability Enhancement of Drug Layered Pellets in a Fixed Dose Combination Tablet - Matthew D. Burke; Xiaorong He; Chris Cook; Greg A. Petrov; Susan Long; Mark D. Coffin (AAPS PharmSciTech, 2013)

Niche differentiation and spatial partitioning in the evolution of two Australian monsoon tropical tree species - Robert D. Edwards; Michael D. Crisp; Lyn G. Cook (Journal of Biogeography, 2013)
Aim Geographical and climatic barriers to organismal dispersal and distribution play a major role in speciation. We use a sister‐pair of widespread savanna trees ( M elaleuca argentea and M . fluviatilis ) to test the influence of putative barriers on divergence within and between species across an otherwise continuous landscape. Location The A ustralian monsoon tropics ( AMT ). Methods Chloroplast and nuclear DNA sequences were used to estimate variation between and within species. Hypotheses invoking vicariance and ecological speciation as the mechanisms of divergence between species were explicitly tested using ecological niche modelling. Results We found little evidence for divergence across the C arpentaria B asin, although some chloroplast DNA haplotypes were restricted to regions to the east or west. Pilbara populations were distinct from those to the east across the Great Sandy Desert, including those from the Kimberley. There was a complex pattern of genetic divergence and niche differentiation among M . argentea and M . fluviatilis within a region of secondary range overlap coincident with currently recognized species boundaries across the Great Dividing Range. Main conclusions The two morphospecies are ecologically and genetically distinct, and maintain those differences in sympatry. Speciation might have occurred in allopatry in separate drainage basins that later came into contact. The P ilbara population appears to be distinct but requires further investigation.

Prediction of piezometric surfaces and drain spacing for horizontal drain design - Diana I. Cook; Paul M. Santi; Jerry D. Higgins (Landslides, 2012)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

Influences of the El Niño Southern Oscillation and the Pacific Decadal Oscillation on the timing of the North American spring - Gregory J. McCabe; Toby R. Ault; Benjamin I. Cook; Julio L. Betancourt; Mark D. Schwartz (International Journal of Climatology, 2012)
Detrended, modelled first leaf dates for 856 sites across North America for the period 1900–2008 are used to examine how the El Niño Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) separately and together might influence the timing of spring. Although spring (mean March through April) ENSO and PDO signals are apparent in first leaf dates, the signals are not statistically significant (at a 95% confidence level ( p p

Hypoxic events stimulate nitrogen recycling in a shallow salt‐wedge estuary: The Yarra River estuary, Australia - Keryn L. Roberts; Vera M. Eate; Bradley D. Eyre; Daryl P. Holland; Perran L. M. Cook (Limnology and Oceanography, 2012)
The Yarra River estuary is a salt‐wedge estuary prone to periods of stratification‐induced anoxia and hypoxia (O 2 −1 ) during low‐flow events. Nitrate reduction pathways were examined using the 15 N isotope pairing technique in intact sediment cores, emulating in situ conditions, to evaluate the fate of NO during changing oxygen conditions. Water‐column concentrations of dissolved inorganic carbon (DIC), O 2 , NH, and NO x (NO + NO) were also measured to examine any deviation from conservative behavior (denoted Δ) in response to oxygen variability within the estuary. The estuary was a source of NH in the anoxic bottom waters. Whole‐system estimates using deviations from conservative behavior and core incubations were in good agreement and showed that NH was regenerated more efficiently relative to DIC under hypoxic conditions. For the whole system, mean ΔDIC : ΔNH ratios under oxic (85 ± 33) and hypoxic (20 ± 3) conditions were significantly different. The more‐efficient NH regeneration during hypoxia was attributed to rapid mineralization rates and cessation of nitrification; dissimilatory nitrate reduction to ammonium (DNRA) was not a significant contributor. Unexpectedly, the denitrification : DNRA ratio was significantly higher under hypoxic conditions, with denitrification contributing 99.1% ± 0.3% of total nitrate reduction. DNRA rates were significantly higher during oxic conditions (123.5 ± 30.7 µmol m −2 h −1 ) when compared with rates during hypoxia (0.6 ± 0.1 µmol m −2 h −1 ). The increase in DNRA in the presence of oxygen was attributed to the alleviation of NO limitation during these conditions.

The “salt wedge pump”: Convection‐driven pore‐water exchange as a source of dissolved organic and inorganic carbon and nitrogen to an estuary - Isaac R. Santos; Perran L. M. Cook; Louissa Rogers; Jason de Weys; Bradley D. Eyre (Limnology and Oceanography, 2012)
Hypoxia and anoxia in coastal waters have typically been explained by the respiration of sinking organic matter associated with nutrient over‐enrichment and phytoplankton blooms. Here, we assess whether submarine groundwater discharge and seawater recirculation in sediments can explain widespread chemical anomalies, including low dissolved oxygen, in salt wedge estuaries. We rely on high‐resolution radon (a natural groundwater and pore‐water tracer), and dissolved carbon concentrations and stable isotope observations in the Yarra River estuary in Melbourne, Australia. Radon was highly enriched within the salt wedge, demonstrating enhanced pore‐water exchange at this area. We use the term “salt wedge pump” to describe convection‐driven advective pore‐water exchange at the sediment–water interface during the upstream propagation of the salt wedge. Radon‐derived convection‐driven pore‐water exchange rates within the salt wedge were estimated at 2.8 cm d −1 , a value equivalent to 2.4% of the total river freshwater runoff to the estuary. Pore‐water exchange led to pulsed dissolved inorganic carbon (DIC) and ammonium fluxes ∼ 10‐fold higher than measured diffusive fluxes. In contrast, diffusive sediment oxygen uptake was 5‐fold higher than oxygen uptake related to advective pore‐water exchange. Estimated fluxes, associated with the nonconservative DIC, δ 13 C‐DIC, and ammonium behavior within the estuary support convective pore‐water exchange as a major source of DIC and ammonium to the estuary, but not of dissolved organic carbon, nitrate, dissolved organic nitrogen, and anoxia. Accounting for seawater recirculation in sediments may help reconcile unbalanced carbon and nitrogen budgets in several coastal systems.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Influence of Phenological Stage on Swainsonine and Endophyte Concentrations in Oxytropis sericea - Daniel Cook; Lei Shi; Dale R. Gardner; James A. Pfister; Daniel Grum; Kevin D. Welch; Michael H. Ralphs (Journal of Chemical Ecology, 2012)

Phylogeography of related diadromous species in continental and island settings, and a comparison of their potential and realized dispersal patterns - Benjamin D. Cook; Timothy J. Page; Jane M. Hughes (Journal of Biogeography, 2012)
Aim To compare patterns of potential and realized dispersal in ecologically similar and phylogenetically related amphidromous shrimps (Atyidae) in continental and island‐dominated landscapes. Location Eastern Australia and the Caribbean region. Methods Population genetic and phylogeographic analyses of mitochondrial DNA data for Australatya striolata from eastern Australia (a continental landscape) and Atya scabra from the Caribbean (an island‐dominated landscape). Results Australatya striolata contained two highly divergent genetic lineages in eastern Australia, corresponding to the disjunct northern and southern populations, respectively. These lineages probably represent allopatric cryptic species, both of which were found to have genetically homogeneous population structures within their regions of occurrence. Atya scabra was genetically homogeneous throughout the Caribbean. Recent population expansions were detected for Atya scabra in the Caribbean, but not for northern or southern Australatya striolata . Main conclusions The findings of this study are consistent with previously reported patterns of genetic population structure in amphidromous species in both continental and island‐dominated landscapes, suggesting that potential for widespread dispersal is typically matched by realized patterns of panmixia. We therefore raise the hypothesis that landscape setting (i.e. continent or island‐dominated) does not influence dispersal patterns in amphidromous species. Further studies, especially of population genetic patterns of amphidromous species on continents, are needed to test this idea. Interestingly, results of the genetic neutrality tests led us to hypothesize that demographic and drift‐mutation equilibrium is attainable although not always evident for amphidromous species on continents, but is not attainable for those species distributed across island settings.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The Importance of Termites to the CH4 Balance of a Tropical Savanna Woodland of Northern Australia - Hiz Jamali; Stephen J. Livesley; Samantha P. Grover; Tracy Z. Dawes; Lindsay B. Hutley; Garry D. Cook; Stefan K. Arndt (Ecosystems, 2011)

The perception of harmonic triads: an fMRI study - Takashi X. Fujisawa; Norman D. Cook (Brain Imaging and Behavior, 2011)

Nucleic Acid Amplification-Based Methods for Detection of Enteric Viruses: Definition of Controls and Interpretation of Results - Martin D’Agostino; Nigel Cook; David Rodriguez-Lazaro; Saskia Rutjes (Food and Environmental Virology, 2011)

Development and use of genic molecular markers (GMMs) for construction of a transcript map of chickpea (Cicer arietinum L.) - Neha Gujaria; Ashish Kumar; Preeti Dauthal; Anuja Dubey; Pavana Hiremath; A. Bhanu Prakash; Andrew Farmer; Mangla Bhide; Trushar Shah; Pooran M. Gaur; Hari D. Upadhyaya; Sabhyata Bhatia; et al. (Theoretical and Applied Genetics, 2011)

Optimal Fire Regimes for Soil Carbon Storage in Tropical Savannas of Northern Australia - Anna E. Richards; Garry D. Cook; Brian T. Lynch (Ecosystems, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Soil Carbon Characteristics in Two Mississippi River Deltaic Marshland Profiles - Jim J. Wang; Syam K. Dodla; Ronald D. DeLaune; Wayne H. Hudnall; Robert L. Cook (Wetlands, 2011)

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Population structure and linkage disequilibrium in oat (Avena sativa L.): implications for genome-wide association studies - M. A. Newell; D. Cook; N. A. Tinker; J.-L. Jannink (Theoretical and Applied Genetics, 2011)

A Novel Shape Memory Alloy Annuloplasty Ring for Minimally Invasive Surgery: Design, Fabrication, and Evaluation - Molly F. Purser; Andrew L. Richards; Richard C. Cook; Jason A. Osborne; Denis R. Cormier; Gregory D. Buckner (Annals of Biomedical Engineering, 2011)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Spatial drought reconstructions for central High Asia based on tree rings - Keyan Fang; Nicole Davi; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Rosanne D’Arrigo (Climate Dynamics, 2010)

Rainbow trout Oncorhynchus mykiss consume less energy when swimming near obstructions - C. L. Cook; D. J. Coughlin (Journal of Fish Biology, 2010)
The effect of obstructions in steady flow on swimming by rainbow trout Oncorhynchus mykiss was examined in a respirometry swim tunnel to test the prediction that fish interacting with obstructions require less energy to hold station. When an obstruction was present, O. mykiss altered the kinematics of swimming and the rate of oxygen consumption was significantly reduced. The fish employed both entrainment and Kármán gait swimming strategies, permitting greater locomotor efficiency.

Dating of ‘young’ groundwaters using environmental tracers: advantages, applications, and research needs - Brent D. Newman; Karsten Osenbrück; Werner Aeschbach-Hertig; D. Kip Solomon; Peter Cook; Kazimierz Różański; Rolf Kipfer (Isotopes in Environmental and Health Studies, 2010)

Reconstructed droughts for the southeastern Tibetan Plateau over the past 568 years and its linkages to the Pacific and Atlantic Ocean climate variability - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Nicole Davi (Climate Dynamics, 2010)

Negative feedback in the cold: ice retreat produces new carbon sinks in Antarctica - L. S. PECK; D. K. A. BARNES; A. J. COOK; A. H. FLEMING; A. CLARKE (Global Change Biology, 2010)
Feedbacks on climate change so far identified are predominantly positive, enhancing the rate of change. Loss of sea‐ice, increase in desert areas, water vapour increase, loss of tropical rain forest and the restriction of significant areas of marine productivity to higher latitude (thus smaller geographical zones) all lead to an enhancement of the rate of change. The other major feedback identified, changes in cloud radiation, will produce either a positive feedback, if high level clouds are produced, or a negative feedback if low level clouds are produced. Few significant negative feedbacks have been identified, let alone quantified. Here, we show that the loss of ice shelves and retreat of coastal glaciers around the Antarctic Peninsula in the last 50 years has exposed at least 2.4 × 10 4 km 2 of new open water. We estimate that these new areas of open water have allowed new phytoplankton blooms containing a total standing stock of ∼5.0 × 10 5 tonnes of carbon to be produced. New marine zooplankton and seabed communities have also been produced, which we estimate contain ∼4.1 × 10 5 tonnes of carbon. This previously unquantified carbon sink acts as a negative feedback to climate change. New annual productivity, as opposed to standing stock, amounts to 3.5 × 10 6 tonnes yr −1 of carbon, of which 6.9 × 10 5 tonnes yr −1 deposits to the seabed. By comparison the total aboveground biomasses of lowland American tropical rainforest is 160–435 tonnes ha −1 . Around 50% of this is carbon. On this basis the carbon held in new biomass described here is roughly equivalent to 6000–17 000 ha of tropical rainforest. As ice loss increases in polar regions this feedback will become stronger, and eventually, over thousands to hundreds of thousands of years, over 50 Mtonnes of new carbon could be fixed annually in new coastal phytoplankton blooms and over 10 Mtonnes yr −1 locked in biological standing stock around Antarctica.

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

Immigration history of amphidromous species on a Greater Antillean island - Benjamin D. Cook; Catherine M. Pringle; Jane M. Hughes (Journal of Biogeography, 2010)
Aim To use molecular data to test for dispersal structuring in the immigration history of an amphidromous community on an island. Location The Caribbean island of Puerto Rico. Methods Mitochondrial DNA sequences were obtained from 11 amphidromous species, including shrimps, fish and a gastropod, sampled from throughout the island. The timing of population expansion ( T E ) in each species was calculated using nucleotide variation and molecular clock dating methods. The order of species accumulation was then reconstructed (oldest to most recent estimate for T E ), and groups of species with non‐overlapping estimates for T E were identified. The temporal span and average immigration rate for each group were calculated and compared with expectations of two previously published models of island immigration [the ‘dispersal‐structured model of island recolonization’ ( Whittaker & Jones, Oikos , 1994 , 69 , 524–529), which predicts short phases of rapid immigration followed by extended phases with relatively slow immigration rates; and the ‘colonization window hypothesis’ ( Carine, Taxon , 2005 , 54 , 895–903), which suggests that opportunities for island colonization are temporally constrained to discrete waves of colonization]. Results The molecular data indicated the immigration history of Puerto Rican amphidromous fauna from the late Pleistocene through the Holocene and identified two groups of species with non‐overlapping estimates for T E and one group that overlapped with the other two groups. The temporal span, average immigration rate and lack of discreteness between all three groups indicated a continuum of immigration rather than distinct phases of species arrivals. Main conclusions This study did not support the expectations of the immigration models and suggested that amphidromous species from Puerto Rico comprise a single class of marine‐based dispersers. The immigration sequence we report probably reflects a recolonization chronology in this community, in keeping with the notion of species turnover through time. Four areas of future research into the immigration history of amphidromous species on islands are identified, and indicated the possibility that equilibrium processes govern long‐term community change in amphidromous biota on islands.

Textural variation in the pyrite-rich ore deposits of the Røros district, Trondheim Region, Norway: implications for pyrite deformation mechanisms - Craig D. Barrie; Nigel J. Cook; Alan P. Boyle (Mineralium Deposita, 2010)

Reconstructing ENSO: the influence of method, proxy data, climate forcing and teleconnections - Rob Wilson; Edward Cook; Rosanne D'Arrigo; Nadja Riedwyl; Michael N. Evans; Alexander Tudhope; Rob Allan (Journal of Quaternary Science, 2010)
In this study we compare three newly developed independent NINO3.4 sea surface temperature (SST) reconstructions using data from (1) the central Pacific (corals), (2) the TexMex region of the USA (tree rings) and (3) other regions in the Tropics (corals and an ice core) which are teleconnected with central Pacific SSTs in the 20th century. Although these three reconstructions are strongly calibrated and well verified, inter‐proxy comparison shows a significant weakening in inter‐proxy coherence in the 19th century. This breakdown in common signal could be related to insufficient data, dating errors in some of the proxy records or a breakdown in El Niño–Southern Oscillation's (ENSO's) influence on other regions. However, spectral analysis indicates that each reconstruction portrays ENSO‐like spectral properties. Superposed epoch analysis also shows that each reconstruction shows a generally consistent ‘El Niño‐like’ response to major volcanic events in the following year, while during years T + 4 to T + 7 ‘La Niña‐like’ conditions prevail. These results suggest that each of the series expresses ENSO‐like ‘behaviour’, but this ‘behaviour’ does not appear to be spatially or temporally consistent. This result may reflect published observations that there appear to be distinct ‘types’ of ENSO variability depending on location within the tropical Pacific. Future work must address potential dating issues within some proxies (i.e. sampling of multiple coral heads for one location) as well as assessing the time stability of local climate relationships with central Pacific SSTs. More emphasis is needed on sampling new and extending old coral proxy records from the crucial central and eastern tropical Pacific region. Copyright © 2009 John Wiley & Sons, Ltd. and © Crown Copyright 2009.

The petrogenesis of sodic island arc magmas at Savo volcano, Solomon Islands - D. J. Smith; M. G. Petterson; A. D. Saunders; I. L. Millar; G. R. T. Jenkin; T. Toba; J. Naden; J. M. Cook (Contributions to Mineralogy and Petrology, 2009)

Swainsoninine Concentrations and Endophyte Amounts of Undifilum oxytropis in Different Plant Parts of Oxytropis sericea - Daniel Cook; Dale R. Gardner; Michael H. Ralphs; James A. Pfister; Kevin D. Welch; Benedict T. Green (Journal of Chemical Ecology, 2009)

Phylogenetic endemism: a new approach for identifying geographical concentrations of evolutionary history - DAN ROSAUER; SHAWN W. LAFFAN; MICHAEL D. CRISP; STEPHEN C. DONNELLAN; LYN G. COOK (Molecular Ecology, 2009)
We present a new, broadly applicable measure of the spatial restriction of phylogenetic diversity, termed phylogenetic endemism (PE). PE combines the widely used phylogenetic diversity and weighted endemism measures to identify areas where substantial components of phylogenetic diversity are restricted. Such areas are likely to be of considerable importance for conservation. PE has a number of desirable properties not combined in previous approaches. It assesses endemism consistently, independent of taxonomic status or level, and independent of previously defined political or biological regions. The results can be directly compared between areas because they are based on equivalent spatial units. PE builds on previous phylogenetic analyses of endemism, but provides a more general solution for mapping endemism of lineages. We illustrate the broad applicability of PE using examples of Australian organisms having contrasting life histories: pea‐flowered shrubs of the genus Daviesia (Fabaceae) and the Australian species of the Australo‐Papuan tree frog radiation within the family Hylidae.

Convergence of tree water use within an arid-zone woodland - A. P. O’Grady; P. G. Cook; D. Eamus; A. Duguid; J. D. H. Wischusen; T. Fass; D. Worldege (Oecologia, 2009)

Moisture variability across China and Mongolia: 1951–2005 - Jinbao Li; Edward R. Cook; Rosanne D’arrigo; Fahu Chen; Xiaohua Gou (Climate Dynamics, 2009)

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity - Daniel Cook; Dale R. Gardner; James A. Pfister; Kevin D. Welch; Benedict T. Green; Stephen T. Lee (Journal of Chemical Ecology, 2009)

An Investigation into the Rheology of Pharmaceutical Inter-granular Material Bridges at High Shear Rates - Barry Crean; Xinyong Chen; Simon R. Banks; Walter G. Cook; Colin D. Melia; Clive J. Roberts (Pharmaceutical Research, 2009)

A Dynamic Heart System to Facilitate the Development of Mitral Valve Repair Techniques - Andrew L. Richards; Richard C. Cook; Gil Bolotin; Gregory D. Buckner (Annals of Biomedical Engineering, 2009)

Is (−)-Catechin a Novel Weapon of Spotted Knapweed (Centaurea stoebe)? - Stephen O. Duke; Amy C. Blair; Franck E. Dayan; Robert D. Johnson; Kumudini M. Meepagala; Daniel Cook; Joanna Bajsa (Journal of Chemical Ecology, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Common tree growth anomalies over the northeastern Tibetan Plateau during the last six centuries: implications for regional moisture change - JINBAO LI; EDWARD R. COOK; ROSANNE D'ARRIGO; FAHU CHEN; XIAOHUA GOU; JIANFENG PENG; JIANGUO HUANG (Global Change Biology, 2008)
The world's hydrological cycle is believed to intensify with global warming, yet current climate models have only a limited ability to assess moisture responses at regional scales. Tree‐ring records are a valuable source of information for understanding long‐term, regional‐scale moisture changes, particularly for large regions such as the Tibetan Plateau (TP), where the observational data are short and sparse. Here, we present a new ring‐width chronology developed from Qilian Juniper ( Sabina przewalskii ) wood at two sites on the northeastern TP. This chronology, combined with others from the same region, demonstrates that tree growth anomalies are linked to regional late spring to early summer moisture availability. Although late monsoon season precipitation in the study area decreased during recent decades, tree growth continued to increase due to persistent moisture availability in the early monsoon season. Comparison with global sea surface temperatures (SSTs) indicates that early (late) monsoon season precipitation is closely related to tropical Pacific (Indian Ocean) SSTs, suggesting a possible seasonal shift in the dominant moisture source area for monsoonal precipitation over the northeastern TP. It is further shown that there is a very high degree of coherency regarding low‐frequency tree growth anomalies over the northeastern TP during the last six centuries. The most prominent drought epoch occurred during ca. 1450–1500, which may have been caused by a significant decrease in the thermal gradient between the Eurasian continent and the tropical oceans. A persistent tree growth increase since the 1880s is coincident with global warming, suggesting an intensified early monsoon season moisture regime in the study area.

Therapeutic frontiers: preventing and treating infectious diseases by inhibiting bacterial quorum sensing - C. A. Martin; A. D. Hoven; A. M. Cook (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Andropogon gayanus (Gamba Grass) Invasion Increases Fire-mediated Nitrogen Losses in the Tropical Savannas of Northern Australia - N. A. Rossiter-Rachor; S. A. Setterfield; M. M. Douglas; L. B. Hutley; G. D. Cook (Ecosystems, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

°Molecular evidence for sequential colonization and taxon cycling in freshwater decapod shrimps on a Caribbean island - BENJAMIN D. COOK; CATHERINE M. PRINGLE; JANE M. HUGHES (Molecular Ecology, 2008)
Taxon cycling, i.e. sequential phases of expansions and contractions in species’ distributions associated with ecological or morphological shifts, are postulated to characterize dynamic biogeographic histories in various island faunas. The Caribbean freshwater shrimp assemblage is mostly widespread and sympatric throughout the region, although one species (Atyidae: Atya lanipes ) is geographically restricted and ecologically and morphologically differentiated from other Atya species. Using patterns of nucleotide variation at the COI mtDNA gene in five species of freshwater shrimp ( A. lanipes , A. scabra , A. innocuous ; Xiphocarididae: Xiphocaris elongata ; Palaemonidae: Macrobrachium faustinum ) from Puerto Rico, we expected to detect a signature of sequential colonization in these shrimp, consistent with the concept of taxon cycling, and expected that A. lanipes would be at a different taxon stage (i.e. an early stage species) to all other species. We also examined patterns of genetic population structure in each species expected with poor, intermediate and well‐developed abilities for among‐river dispersal. Population expansions were detected in all species, although the relative timing of the expansions varied among them. Assuming that population expansions followed colonization of Puerto Rico by freshwater shrimp, results bear the hallmarks of sequential colonization and taxon cycling in this fauna. A. lanipes had a star phylogeny, low mean pairwise nucleotide differences and recent (Holocene) estimates for an in situ population expansion in Puerto Rico, and it was inferred as an early stage species in the taxon cycle undergoing a secondary phase of expansion. All other species were inferred as late stage species undergoing regional population expansions, as their mean pairwise nucleotide differences were relatively high and phylogenetic patterns were more complex than A. lanipes . High rates of gene flow without isolation by distance among rivers were detected in all species, although results should be treated cautiously as some populations are unlikely to be in mutation–drift equilibrium. Nested clade analysis produced inconsistent results among species that all have high rates of gene flow and expanding populations.

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Len Muscatine (1932–2007) and his contributions to the understanding of algal-invertebrate endosymbiosis - O. Hoegh-Guldberg; G. Muller-Parker; C. B. Cook; R. D. Gates; E. Gladfelter; R. K. Trench; V. M. Weis (Coral Reefs, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Soil–water and solute movement under precision irrigation: knowledge gaps for managing sustainable root zones - S. R. Raine; W. S. Meyer; D. W. Rassam; J. L. Hutson; F. J. Cook (Irrigation Science, 2007)

Genotyping of phenotypically defined cells in neoplasia: enhanced immunoFISH via tyramide signal amplification (TSA) segregates immunophenotypically—defined cell populations for gated genotyping - Raymond R. Tubbs; Kingshuk Das; James R. Cook; James D. Pettay; Patrick C. Roche; Thomas Grogan (Journal of Molecular Histology, 2007)

Behavioural and chemical ecology underlying the success of turnip rape (Brassica rapa) trap crops in protecting oilseed rape (Brassica napus) from the pollen beetle (Meligethes aeneus) - S. M. Cook; H. B. Rasmussen; M. A. Birkett; D. A. Murray; B. J. Pye; N. P. Watts; I. H. Williams (Arthropod-Plant Interactions, 2007)

Blood cells of Murray cod Maccullochella peelii peelii (Mitchell) - S. Shigdar; D. Cook; P. Jones; A. Harford; A. C. Ward (Journal of Fish Biology, 2007)
Analysis of the peripheral blood cells of Murray cod Maccullochella peelii peelii identified seven distinct subpopulations including a novel basophilic cell. Haematological reference ranges were established to facilitate future diagnostic blood sampling of this fish.

The effect of polymorphism at the serotonin transporter gene on decision-making, memory and executive function in ecstasy users and controls - Jonathan P. Roiser; Robert D. Rogers; Lynnette J. Cook; Barbara J. Sahakian (Psychopharmacology, 2006)

Populations of Myriophyllum alterniflorum L. as bioindicators of pollution in acidic to neutral rivers in the Limousin region - P. Chatenet; D. Froissard; J. Cook-Moreau; P. Hourdin; A. Ghestem; M Botineau; J. Haury (Hydrobiologia, 2006)

Fire Frequency and Mosaic Burning Effects on a Tallgrass Prairie Ground Beetle Assemblage - William M. Cook; Robert D. Holt (Biodiversity and Conservation, 2006)

Beaked whale auditory evoked potential hearing measurements - Mandy L. H. Cook; René A. Varela; Juli D. Goldstein; Stephen D. McCulloch; Gregory D. Bossart; James J. Finneran; Dorian Houser; David A. Mann (Journal of Comparative Physiology A, 2006)

Biogeographic history of an Australian freshwater shrimp, Paratya australiensis (Atyidae): the role life history transition in phylogeographic diversification - B. D. COOK; A. M. BAKER; T. J. PAGE; S. C. GRANT; J. H. FAWCETT; D. A. HURWOOD; J. M. HUGHES (Molecular Ecology, 2006)
The widespread distribution of the freshwater shrimp Paratya australiensis in eastern Australia suggests that populations of this species have been connected in the past. Amphidromy is ancestral in these shrimps, although many extant populations are known to be restricted to freshwater habitats. In this study, we used a fragment of the cytochrome c oxidase I mitochondrial DNA (mtDNA) gene to examine diversity within P. australiensis and to assess the relative importance of amphidromy in its evolutionary history. We hypothesized that if transitions from an amphidromous to a freshwater life history were important, then we would find a number of divergent lineages restricted to single or groups of nearby drainages. Alternatively, if amphidromy was maintained within the species historically, we expected to find lineages distributed over many drainages. We assumed that the only way for divergence to occur within amphidromous lineages was if dispersal was limited to between nearby estuaries, which, during arid periods in the earth's history, became isolated from one another. We found nine highly divergent mtDNA lineages, estimated to have diverged from one another in the late Miocene/early Pliocene, when the climate was more arid than at present. Despite this, the geographic distribution of lineages and haplotypes within lineages did not support the notion of a stepping‐stone model of dispersal between estuaries. We conclude that the extensive divergence has most likely arisen through a number of independent amphidromy–freshwater life history transitions, rather than via historical isolation of amphidromy populations. We also found evidence for extensive movement between coastal and inland drainages, supporting the notion that secondary contact between lineages may have occurred as a result of drainage rearrangements. Finally, our data indicate that P. australiensis is likely a complex of cryptic species, some of which are widely distributed, and others geographically restricted.

Effects of combining ethanol (EtOH) with gamma-hydroxybutyrate (GHB) on the discriminative stimulus, locomotor, and motor-impairing functions of GHB in mice - Charles D. Cook; Laura Biddlestone; Andrew Coop; Patrick M. Beardsley (Psychopharmacology, 2006)

Bidirectional effects of benzodiazepine binding site ligands on active avoidance acquisition and retention: differential antagonism by flumazenil and β-CCt - Miroslav M. Savić; Dragan I. Obradović; Nenad D. Ugrešić; James M. Cook; P. V. V. S. Sarma; Dubravko R. Bokonjić (Psychopharmacology, 2005)

Directional asymmetry of long‐distance dispersal and colonization could mislead reconstructions of biogeography - Lyn G. Cook; Michael D. Crisp (Journal of Biogeography, 2005)
Aim Phylogenies are increasingly being used to attempt to answer biogeographical questions. However, a reliance on tree topology alone has emerged without consideration of earth processes or the biology of the organisms in question. Most ancestral‐state optimization methods have inherent problems, including failure to take account of asymmetry, such as unequal probabilities of losses and gains, and the lack of use of independent cost estimates. Here we discuss what we perceive as shortcomings in most current tree‐based biogeography interpretation methods and show that consideration of processes and their likelihoods can turn the conventional biogeographical interpretation on its head. Location Southern hemisphere focus but applicable world‐wide. Methods The logic of existing methods is reviewed with respect to their adequacy in modelling processes such as geographical mode of speciation and likelihood of dispersal, including directional bias. Published reconstructions of dispersal of three plant taxa between Australia and New Zealand were re‐analysed using standard parsimony and maximum likelihood (ML) methods with rate matrices to model expected asymmetry of dispersal. Results Few studies to date incorporate asymmetric dispersal rate matrices or question the simplistic assumption of equal costs. Even when they do, cost matrices typically are not derived independently of tree topology. Asymmetrical dispersal between Australia and New Zealand could be reconstructed using parsimony but not with ML. Main conclusions The inadequacy of current models has important consequences for our interpretation of southern hemisphere biogeography, particularly in relation to dispersal. For example, if repeated directional dispersals and colonization in the direction of prevailing winds have occurred, with intervening periods of speciation, then there is no need to infer dispersals against those winds. Failure to take account of directionality and other biases in reconstruction methods has implications beyond the simple misinterpretation of the biogeography of a taxonomic group, such as calibration of molecular clocks, the dating of vicariance events, and the prioritization of areas for conservation.

Historical transoceanic dispersal of a freshwater shrimp: the colonization of the South Pacific by the genus Paratya (Atyidae) - Timothy J. Page; Andrew M. Baker; Benjamin D. Cook; Jane M. Hughes (Journal of Biogeography, 2005)
Aim To infer the phylogenetic relationships within the freshwater shrimp genus Paratya Miers, 1882 (Atyidae) and to use these data to answer biogeographical questions about the location, timing and form of evolution of this genus in the South Pacific. Location Paratya are spread throughout various freshwater habitats in the western Pacific, with a disjunct northern range in the North Pacific (Japan, Korea, Ryukyu Islands, Siberia) and South Pacific (Australia, New Zealand, New Caledonia, Lord Howe, Norfolk Island). Methods Specimens were obtained from throughout its range. Mitochondrial sequences of cytochrome oxidase subunit I and 16S ribosomal DNA were analysed using phylogenetic techniques to identify whether landmasses are monophyletic and what the relationships are between landmasses. Molecular clock dating methods were used to date divergences between taxa. Results Each landmass was recovered as monophyletic. Japan/Ryukyu Islands is the most basal group, followed by New Zealand. Australian specimens form a sister group to a clade made up of two groups (New Caledonia and Lord Howe/Norfolk Island). The oldest divergence within the genus (between North and South Pacific) took place 12 –19 Ma. Main conclusions The geographical origin of the genus (either Gondwana or Laurasia) is unclear. Dispersal occurred between the North and South Pacific long after the split up of Gondwana. Dispersal likely explains the presence of Paratya on each landmass in the South Pacific, from continent to isolated oceanic island. This dispersal is conjectured to have taken place through oceanic currents because of the amphidromous life cycle of some taxa of Paratya , given that amphyidromy is plesiomorphic in atyid shrimp.

High-quality RNA, cDNA, and derived EST libraries from grapevine (Vitis vinifera L.) - A. B. Iandolino; F. Goes da Silva; H. Lim; H. Choi; L. E. Williams; D. R. Cook (Plant Molecular Biology Reporter, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

The severe combined immunodeficient (SCID) mouse model of human immunodeficiency virus encephalitis: Deficits in cognitive function - William C Griffin; Lawrence D Middaugh; Jennifer E Cook; William R Tyor (Journal of NeuroVirology, 2004)

Dendroclimatic signals in long tree‐ring chronologies from the Himalayas of Nepal - Edward R. Cook; Paul J. Krusic; Philip D. Jones (International Journal of Climatology, 2003)
We describe the development of a tree‐ring chronology network in Nepal that is suitable for reconstructing temperature‐related climate forcing over the past few hundred years. The network is composed of 32 tree‐ring chronologies and is represented by five indigenous tree species. An empirical orthogonal function analysis of the chronologies over the common interval 1796–92 indicates the existence of coherent large‐scale signals among the tree‐ring chronologies that are hypothesized to reflect, in part, broad‐scale climate forcing related to temperatures. A long monthly temperature record for Kathmandu is developed and used to test this hypothesis. In so doing, significant monthly and seasonal temperature responses are identified that provide guidance for the formal reconstruction of two temperature seasons: February–June (1546–91) and October–February (1605–91). Each reconstruction indicates the occurrence of unusually cold temperatures in 1815–22, which coincides with the eruption of Tambora in Indonesia. A novel method is also used to add probable missing multi‐centennial temperature variance to each reconstruction. The resulting ‘adjusted’ reconstructions strongly reflect patterns of temperature variability associated with Little Ice Age cooling and warming into the 20th century, with the October–February season exhibiting the strongest increase in temperature over the past ∼400 years. Only the October–February season shows any evidence for late‐ 20th century warming, whereas February–June temperatures have actually cooled since 1960 (as with the observational series). Copyright © 2003 Royal Meteorological Society

Deep Natural Gas Resources - T. S. Dyman; R. E. Wyman; V. A. Kuuskraa; M. D. Lewan; T. A. Cook (Natural Resources Research, 2003)

American marten ( Martes americana ) in the Pacific Northwest: population differentiation across a landscape fragmented in time and space - Maureen P. Small; Karen D. Stone; Joseph A. Cook (Molecular Ecology, 2003)
American marten ( Martes americana ) have a close association with mature temperate forests, a habitat that expanded throughout the Pacific Northwest as glaciers receded at the end of the Pleistocene. Similar to several other forest‐associated mammals in North America (e.g. black bear), genetic analysis of the marten shows a deep phylogeographical subdivision that reflects populations with distinctive evolutionary histories. Using a suite of 14 microsatellite markers, we explored the genetic structure of marten populations in two reciprocally monophyletic clades in the Pacific Northwest identified previously as M. caurina and M. americana by mitochondrial haplotypes and morphology. Microsatellite phylogeographical patterns were congruent with mitochondrial analyses. These independent data sets shed light upon hybridization patterns, population structure and evolutionary histories. Hybridization between M. caurina and M. americana individuals was documented in two regions of sympatry (Kuiu Island in southeastern Alaska and southern Montana). Northern insular populations of M. caurina exhibited higher differentiation and lower variability relative to northern populations of M. americana . Greater divergence among M. caurina populations may reflect longer isolation and persistence in coastal forest habitat that was fragmented by rising sea level in the early Holocene. Lower differentiation among northern M. americana populations and close relationship to other continental M. americana populations may reflect more recent expansion into the Pacific Northwest and/or continued gene flow among populations. Differentiation among M. caurina populations was attributed to habitat fragmentation (i.e. rising sea level), as opposed to isolation‐by‐distance; oceanic straits pose significant barriers to gene flow among M. caurina populations and between populations of M. caurina and M. americana .

Post‐glacial colonization of northwestern North America by the forest‐associated American marten ( Martes americana , Mammalia: Carnivora: Mustelidae) - Karen D. Stone; Rodney W. Flynn; Joseph A. Cook (Molecular Ecology, 2002)
Phylogeographic patterns were used to assess intraspecific diversification of American martens ( Martes americana ). Within martens, two morphological groups ( americana and caurina ) have been recognized, though the level of distinction between them has been debated. We examined mitochondrial cytochrome b gene haplotypes from 680 martens to explore the colonization history of the Pacific Northwest and found two clades that correspond to the morphological groups. The widespread americana clade extends from interior Alaska south to Montana and eastward to Newfoundland and New England (i.e. northwestern, north‐central and northeastern North America). The caurina clade occurs in western North America, minimally extending from Admiralty Island (southeastern Alaska) south to Oregon and Wyoming. Our data indicated two colonization events for the Pacific Northwest (one by members of each clade) and were consistent with the persistence of populations throughout past glacial periods in eastern and western refugia. Due to vegetational and geological history following the past deglaciation, we hypothesize that martens of the caurina clade spread along the North Pacific Coast, and into southeastern Alaska, earlier than martens of the americana clade. Mismatch distributions for the americana clade were indicative of populations that recently experienced demographic expansion, while mismatch distributions for the caurina clade suggested that populations were at equilibrium. These clades are reciprocally monophyletic and distinctive (interclade divergence ranged from 2.5 to 3.0% (uncorrected p ), whereas, intraclade divergence was

Island theory, matrix effects and species richness patterns in habitat fragments - William M. Cook; Kurt T Lane; Bryan L. Foster; Robert D. Holt (Ecology Letters, 2002)
Island biogeography theory, created initially to study diversity patterns on islands, is often applied to habitat fragments. A key but largely untested assumption of this application of theory is that landscape matrix species composition is non‐overlapping with that of the islands. We tested this assumption in successional old field patches in a closely mowed matrix, and because our patches are appropriately viewed as sets of contiguous habitat units we studied patterns of species richness per unit area. Previous studies at our site did not find that diversity patterns on patch ‘islands’ conformed to predictions of island biogeography theory. Our results indicate that when matrix species are removed from the patch samples, diversity patterns conform better to theory. We suggest that classical island theory remains an appropriate tool to study diversity patterns in fragmented habitats, but that allowances should be made for spill‐over colonization of ‘islands’ from the ‘sea’.

Towards a physiology of epithelial pathogens - D. I. Cook; J. A (Pflügers Archiv - European Journal of Physiology, 2002)

Isolation and growth of a cytopathic agent from multiple sclerosis brain tissue - Anthony R White; Nichole S Dutton; Robert D Cook (Journal of NeuroVirology, 2002)

Cocaine-like discriminative stimulus effects of novel cocaine and 3-phenyltropane analogs in the rat - Charles D. Cook; Ivy F. Carroll; Patrick M. Beardsley (Psychopharmacology, 2001)

Spatial variation in the duration of the rainy season in monsoonal Australia - Garry D. Cook; Richard G. Heerdegen (International Journal of Climatology, 2001)
Climatological research in the tropics of northern Australia has focused particularly on the Australian summer monsoon. However, the timing of many ecologically important processes is determined not by the monsoon but by extra‐monsoonal rainfall events. These events produce a temporal pattern of wet and dry spells that is at least as important ecologically as the amount of rain. We defined the rainy season as that period when the probability of 10‐day dry spells was less than 0.5, and the wet season as that period within the rainy season when the probability of dry spells was less than 0.1. We applied these criteria to seven stations along a strong north–south rainfall gradient spanning more than 12° of latitude in tropical north Australia. The duration of the rainy and wet seasons in northern Australia decreases with increasing latitude. The timing and duration of these seasons were also affected by the El Niño–Southern Oscillation (ENSO). The relative contribution of temporally isolated rainfall events to both the duration of the rainy season and the amount of rainfall increases with latitude. The geographic variation in these seasons corresponds to many patterns occurring in natural ecosystems. We argue that understanding the extra‐monsoon rainfall events is critical to understanding how climate variation affects natural ecosystems. Copyright © 2001 Royal Meteorological Society

The age of fine-root carbon in three forests of the eastern United States measured by radiocarbon - J. Gaudinski; S. Trumbore; E. Davidson; A. Cook; D. Markewitz; D. Richter (Oecologia, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

Spatial variability in oviposition damage by periodical cicadas in a fragmented landscape - William M. Cook; Robert D. Holt; Jin Yao (Oecologia, 2001)

Molecular analysis of the genotype-phenotype relationship in factor VII deficiency - D. Millar; G. Kemball-Cook; J. McVey; E. Tuddenham; A. Mumford; G. Attock; J. Reverter; N. Lanir; L. Parapia; J. Reynaud; E. Meili; A. von Felton; et al. (Human Genetics, 2000)

Phytosociological analysis of restored and managed grassland habitat within an urban national park - Andrew M. Greller; Celestine Durando; Leslie F. Marcus; D. Siril A. Wijesundara; Michael D. Byer; Robert Cook; John T. Tanacredi (Urban Ecosystems, 2000)

The dopamine D3/2 agonist 7-OH-DPAT attenuates the development of morphine tolerance but not physical dependence in rats - Charles D. Cook; Andrew C. Barrett; Chockeo Syvanthong; Mitchell J. Picker (Psychopharmacology, 2000)

Modulatory effects of dopamine D3/2 agonists on kappa opioid-induced antinociception and diuresis in the rat - Charles D. Cook; Andrew C. Barrett; Chockeo Syvanthong; Mitchell J. Picker (Psychopharmacology, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Trans-Tasman Sea climate variability since ad 1740 inferred from middle to high latitude tree-ring data - R. D'Arrigo; E. Cook; R. Villalba; B. Buckley; J. Salinger; J. Palmer; K. Allen (Climate Dynamics, 2000)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

Colorectal cancer incidence in Asian migrants to the United States and their descendants - Danna M. Flood; Noel S. Weiss; Linda S. Cook; Julia C. Emerson; Stephen M. Schwartz; John D. Potter (Cancer Causes & Control, 2000)

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

Bay‐scale population structure in coastal Atlantic cod in Labrador and Newfoundland, Canada - D. E. Ruzzante; J. S. Wroblewski; C. T. Taggart; R. K. Smedbol; D. Cook; S. V. Goddaard (Journal of Fish Biology, 2000)
Polymorphisms at five microsatellite DNA loci provide evidence that Atlantic cod Gadus morhua inhabiting Gilbert Bay, Labrador are genetically distinguishable from offshore cod on the north‐east Newfoundland shelf and from inshore cod in Trinity Bay, Newfoundland. Antifreeze activity in the blood suggests that Gilbert Bay cod overwinter within the Bay. Gilbert Bay cod are also smaller (weight and length) for their age and consequently less fecund for their age, than cod elsewhere within the northern cod complex. The productivity and recruitment potential of coastal cod off Labrador may thus be much lower than that of offshore northern cod or of inshore cod farther south, implying that a more conservative management strategy may be required for cod from coastal Labrador than traditionally practised for northern cod inhabiting less harsh environments. Relatively high F ST and R ST measures of population structure suggest that important barriers to gene flow exist among five components that include two inshore (Gilbert and Trinity Bay) and three offshore cod aggregations on the north‐east Newfoundland Shelf and the Grand Bank. D A and D SW estimates of genetic distance that involve Gilbert Bay cod are approximately three‐ and 10–fold larger, respectively, than estimates not involving Gilbert Bay cod. The differences between inshore cod from Gilbert Bay and Trinity Bay raise the possibility that other genetically distinguishable coastal populations may exist, or may have existed prior to the northern cod fishery collapse. Harvesting strategies for northern cod should recognize the existence of genetic diversity between inshore and offshore components as well as among coastal components.

The activity of the H + -monocarboxylate cotransporter during pre-implantation development in the mouse - E. A. Harding; M. L. Day; C. A. Gibb; M. H. Johnson; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

Sex allocation and local mate competition in Old World non-pollinating fig wasps - Mark D. E. Fellowes; Steve G. Compton; James M. Cook (Behavioral Ecology and Sociobiology, 1999)

Selective attenuation of the antinociceptive effects of μ opioids by the putative dopamine D 3 agonist 7-OH-DPAT - C. D. Cook; J. S. Rodefer; Mitchell J. Picker (Psychopharmacology, 1999)

Use of replication-deficient adenoviruses to study signal transduction pathways. Muscarinic responses in HSG and HT29 epithelial cell lines are mediated by G protein βγ-subunits - P. Poronnik; L. M. O'Mullane; A. D. Conigrave; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

The influence of nematodes on below-ground processes in grassland ecosystems - Richard D. Bardgett; Roger Cook; Gregor W. Yeates; Crystal S. Denton (Plant and Soil, 1999)

Construction of a bacterial artificial chromosome library of Medicago truncatula and identification of clones containing ethylene-response genes - Y.-W. Nam; R. V. Penmetsa; G. Endre; P. Uribe; D. Kim; D. R. Cook (Theoretical and Applied Genetics, 1999)

Molecular Phylogeny of Tuco-Tucos, Genus Ctenomys (Rodentia: Octodontidae): Evaluation of the mendocinus Species Group and the Evolution of Asymmetric Sperm - Guillermo D'Elía; Enrique P. Lessa; Joseph A. Cook (Journal of Mammalian Evolution, 1999)

A nuclear DNA basis for shelf‐ and bank‐scale population structure in northwest Atlantic cod ( Gadus morhua ): Labrador to Georges Bank - D. E. RUZZANTE; C. T. TAGGART; D. COOK (Molecular Ecology, 1998)
Variation at five microsatellite DNA loci scored in ≈ 1300 individuals provided evidence of genetic structure among 14 cod ( Gadus morhua ) populations spanning the range of the species in the northwest (NW) Atlantic. Using D A and D SW measures of genetic distance, as well as F ST and R ST measures of population structure, differences are revealed among populations at continental shelf scales (NE Newfoundland Shelf, Grand Banks, Flemish Cap, Scotian Shelf, Georges Bank) where regions are separated by submarine saddles, channels and trenches. However, we also provide evidence of genetic structure at spawning‐bank scales consistent with variation in oceanographic features and in the spatiotemporal distribution of spawning, each of which may represent barriers to gene flow among geographically contiguous populations inhabiting a highly advective environment. The differences described are consistent with postdispersal spawning fidelity to natal areas, a behaviour that may be facilitated by topographically induced gyre‐like circulations that can act as retention mechanisms. Significant degrees of substructure among neighbouring and contiguous cod populations may be most easily explained by the associated oceanographic features and processes that conceivably form the template for the evolution of the structure. We suggest that bathymetric and hydrodynamic structure represents a rational starting point for developing hypotheses to examine the processes that lead to the genetic structuring of marine fish species.

Cell cycle regulation of a T-type calcium current in early mouse embryos - M. L. Day; M. H. Johnson; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1998)

Multiple independent formations of Tragopogon tetraploids (Asteraceae): evidence from RAPD markers - L. M. COOK; P. S. SOLTIS; S. J. BRUNSFELD; D. E. SOLTIS (Molecular Ecology, 1998)
Polyploidy is widely recognized as a significant force leading to the formation of new plant species. Estimates of the number of angiosperm species with polyploid origins are as high as ≈ 50%; however, in spite of this prevalence, many aspects of polyploid evolution remain poorly understood. Recent studies have suggested that recurrent origins of polyploid species are the rule rather than the exception. The present study is one of only a few designed to quantify the number of independent origins of a polyploid species. The two tetraploid species Tragopogon mirus and T . miscellus (Asteraceae) arose within the past 50 years in the Palouse region of eastern Washington and adjacent northern Idaho. Previous work using morphology, cpDNA and rDNA restriction site analyses, allozymes, cytology, and flavonoid chemistry established that T . mirus had arisen at least five times, and T . miscellus at least twice, on the Palouse. To assess the frequency of multiple origins of these species more rigorously, seven populations of T . mirus and three populations of T . miscellus that were indistinguishable based on previous markers were surveyed using random amplified polymorphic DNA (RAPD) markers; populations of the diploid progenitor species from the same sites were also analysed. Each tetraploid population had a unique RAPD marker profile, suggesting that each population surveyed originated independently of the other populations in the region. Only two of the tetraploid populations combined the RAPD marker profiles of the diploid progenitors occurring at the same site. Both polyploid species, whose ranges and numbers have greatly increased since their formation in the early part of the twentieth century, have formed repeatedly on a local geographical scale and during a short time frame. Furthermore, each tetraploid species is spreading not primarily by dispersal of propagules from a single population of origin, but through repeated, independent polyploidization events that recreate the polyploid taxa.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Exploring Environmental Data in a Highly Immersive Virtual Reality Environment - Dianne Cook; Carolina Cruz-Neira; Bradley D. Kohlmeyer; Uli Lechner; Nicholas Lewin; Laura Nelson; Anthony Olsen; Sue Pierson; Jürgen Symanzik (Environmental Monitoring and Assessment, 1998)

Paramagnetic relaxation of ferric "oxyhydroxide" in Victorian brown coal and its structural implications - S. Bocquet; J. D. Cashion; P. S. Cook (Physics and Chemistry of Minerals, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

Dopaminergic activity and the discriminative stimulus effects of mu opioids in pigeons: importance of training dose and attenuation by the D 3 agonist (±)-7-OH-DPAT - C. D. Cook; Mitchell J. Picker (Psychopharmacology, 1998)

Homology modelling of the catalytic domain of early mammalian protein C: evolution of structural features - A. I. Wacey; M. Krawczak; G. Kemball-Cook; D. N. Cooper (Human Genetics, 1997)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Difference in metabolic profile of potassium canrenoate and spironolactone in the rat: Mutagenic metabolites unique to potassium canrenoate - Chyung S. Cook; Charles L. Hauswald; Grant L. Schoenhard; Charles E. Piper; Arun Patel; Frederick M. Radzialowski; Jeremy D. Hribar; William Aksamit; Pat Finnegan; Roy H. Bible; James A. Oppermann (Archives of Toxicology, 1988)

Detection and prevalence of serotypes of feline syncytial spumaviruses - R. L. P. Flower; G. E. Wilcox; R. D. Cook; T. M. Ellis (Archives of Virology, 1985)

Respiratory nitrate reduction by Desulfovibrio sp. - R. G. L. McCready; W. D. Gould; F. D. Cook (Archives of Microbiology, 1983)

The influence of the bone-implant interface stiffness on stress profiles surrounding Al2O3 and carbon dental implants - C. J. Lavernia; S. D. Cook; A. M. Weinstein; J. J. Klawitter (Annals of Biomedical Engineering, 1982)

Residues and dissipation of 2,4-D and 2,4-DCP in potato tubers - D. W. Bristol; D. C. Nelson; L. W. Cook (American Journal of Potato Research, 1981)

Sectional notes - Frank E. Garrett; Roy M. Barnes; W. Frank McGee; A. H. Eddins; W. B. Ward; Verne C. Beverly; H. A. Reiley; Allan W. Purdy; J. C. Campbell; H. J. Evans; Harold Mattson; O. D. Burke; et al. (American Journal of Potato Research, 1947)